Adhesive composition and adhesive sheet
By using an adhesive composition with a specific block copolymer structure, the problem of insufficient adhesion when supporting a micro semiconductor chip is solved, high adhesion, excellent water resistance and good pickup are achieved, and it is suitable for miniaturization and high density stacking of semiconductor chips.
Patent Information
- Application Number
- CN202480003333.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-29
- Filing Date
- 2024-06-14
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-06-14
AI Technical Summary
The existing cutting tape lacks adhesion when supporting micro semiconductor chips, and has poor water resistance and pickup properties, making it difficult to meet the needs of miniaturization and high-density stacking of semiconductor chips.
An adhesive composition comprising (meth)acrylic resin, a photopolymerization initiator and a crosslinker is used, which improves the water resistance and adhesion of the adhesive through a specific block copolymer structure and reduces the adhesion after ultraviolet irradiation for easy pickup.
It achieves high adhesion and excellent water resistance, and can reduce adhesion and improve pick-up after UV irradiation. It is suitable for cutting and stacking of micro semiconductor chips.
Smart Images

Figure BDA0005231879490000161 
Figure BDA0005231879490000171 
Figure BDA0005231879490000172
Abstract
Description
Technical Field
[0001] The present disclosure relates to an adhesive composition using a (meth)acrylic resin, and also relates to an adhesive sheet, a dicing tape, and a dicing die-bonding integrated film having a cured product of the adhesive composition as an adhesive layer. Background Art
[0002] In the past, blade dicing was used as the main method for manufacturing stacked semiconductor chips from semiconductor wafers using silicon (Si), gallium arsenide (GaAs), etc. as raw materials. In this method, the semiconductor wafer is attached to a dicing tape after a surface circuit formation process and a back grinding process. In the dicing process, a high-speed rotating blade is used to cut and separate (diced) it into tiny semiconductor chips. After the dicing process, the semiconductor wafer is provided to a pickup process for picking up semiconductor chips after a cleaning process. In this pickup process, the adhesive layer of the dicing tape is first irradiated with energy rays such as ultraviolet rays to solidify the adhesive layer, thereby reducing the adhesive force. Then the dicing tape is expanded, lifted from the back with a pin, and the semiconductor chip is picked up by vacuum adsorption.
[0003] In blade dicing, in order to cool the blade that is heated during cutting and remove cutting chips, dicing is often performed while supplying cutting water to the blade. If cutting water seeps between the dicing tape and the semiconductor wafer, the adhesive force is greatly reduced, so the dicing tape is required to have excellent water resistance.
[0004] As a dicing tape with excellent water resistance, for example, Patent Document 1 (Japanese Patent Gazette No. 2012-216841) proposes a dicing tape having an adhesive layer formed on a base resin film, wherein the adhesive layer is formed by adding polypropylene oxide having a specific number average molecular weight to an acrylic polymer having radiation-polymerizable carbon-carbon double bonds in the molecule and a photopolymerization initiator.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2012-216841 Summary of the invention
[0008] Problems to be solved by the invention
[0009] As the dicing tape used in the dicing process, a dicing tape in which an adhesive layer is formed by coating an adhesive such as an acrylic adhesive on a resin film substrate is mainly used. As the dicing tape, it plays a role in preventing the cut semiconductor chip from flying during dicing by supporting the semiconductor wafer. In recent years, as semiconductor chips have been miniaturized, the area on the dicing tape that supports a semiconductor chip has become smaller. Therefore, it is necessary to improve the adhesive force of the dicing tape. In addition, as semiconductor chips are miniaturized, a higher level of water resistance is also required. However, the dicing tape proposed in Patent Document 1 has low adhesive force and is insufficient in supporting tiny chips.
[0010] The present disclosure provides an adhesive composition, which can provide an adhesive sheet having excellent water resistance and sufficient adhesion to an adherend, and having excellent peelability after UV irradiation. In addition, the present disclosure relates to an adhesive sheet, a dicing tape, and a dicing / chip bonding integrated film having a cured product of the above-mentioned adhesive composition as an adhesive layer. More specifically, a dicing tape having excellent water resistance, good dicing performance, and excellent pickup performance after UV irradiation, and a dicing / chip bonding integrated film can be provided.
[0011] Means of solving the problem
[0012] The present disclosure includes the following aspects.
[0013] [1] An adhesive composition comprising a (meth)acrylic resin (A), a photopolymerization initiator (B) and a crosslinking agent (C);
[0014] The (meth)acrylic resin (A) is a diblock copolymer consisting of an X block and a Y block.
[0015] The structural unit ratio (molar ratio) of the X block and the Y block is 40:60 to 95:5,
[0016] The X block comprises a structural unit (M-1) having a hydroxyl group and a structural unit (M-2) having an ethylenically unsaturated group,
[0017] The Y block comprises a SP value of 20 (J / cm 3 ) 1 / 2 The following structural units (M-3) of ethylenically unsaturated compounds (m-3), and optionally one or more structural units selected from structural units (M-1) having a hydroxyl group and structural units (M-2) having an ethylenically unsaturated group,
[0018] At least one of the structural unit (M-1), the structural unit (M-2), and the structural unit (M-3) has a structure derived from a (meth)acryloyloxy group,
[0019] When the total amount of the structural units of the X block is 100 mol%, the total amount of the structural units (M-1) having a hydroxyl group and the structural units (M-2) having an ethylenically unsaturated group in the X block is 18 to 95 mol%.
[0020] When the total amount of the structural units of the Y block is 100 mol %, the total amount of the structural units (M-1) having a hydroxyl group and the structural units (M-2) having an ethylenically unsaturated group in the Y block is 0 to 17 mol %.
[0021] [2] The adhesive composition according to [1], wherein the ratio of the structural unit (M-2) having an ethylenically unsaturated group in the X block is 1 to 60 mol % when the total of the structural units of the X block is 100 mol %.
[0022] [3] The adhesive composition according to [1] or [2], wherein the ratio of the structural unit (M-1) having a hydroxyl group in the X block is 0.1 to 35 mol % when the total of the structural units of the X block is 100 mol %.
[0023] [4] The adhesive composition according to any one of [1] to [3], wherein the structural unit (M-2) having an ethylenically unsaturated group possessed by the X block is a structural unit formed by adding an ethylenically unsaturated compound (a) containing an isocyanate group to a hydroxyl group of a structural unit derived from an ethylenically unsaturated compound (m-1) having a hydroxyl group.
[0024] [5] The adhesive composition according to any one of [1] to [4], wherein the Y block has an SP value of 20 (J / cm 3 ) 1 / 2 The ratio of the structural unit (M-3) of the following ethylenically unsaturated compound (m-3) is 70 mol% or more.
[0025] [6] The adhesive composition according to any one of [1] to [5], wherein the SP value of the Y block is 20 (J / cm 3 ) 1 / 2 The structural unit (M-3) of the following ethylenically unsaturated compound (m-3) is a structural unit derived from a monomer selected from a linear or branched (meth)acrylic acid alkyl ester having an alkyl group with 6 to 30 carbon atoms, a (meth)acrylic acid ester containing an alicyclic skeleton, and styrene.
[0026] [7] The adhesive composition according to any one of [1] to [6], wherein the Y block has a structural unit derived from styrene.
[0027] [8] The pressure-sensitive adhesive composition according to any one of [1] to [7], wherein the X block further has a structural unit derived from a linear or branched alkyl (meth)acrylate having an alkyl group with 1 to 6 carbon atoms.
[0028] [9] The adhesive composition according to any one of [1] to [8], wherein the weight average molecular weight of the (meth)acrylic resin (A) is 1×10 4 ~200×10 4 .
[0029]
[10] The adhesive composition according to any one of [1] to [9], wherein the (meth)acrylic resin (A) has an ethylenically unsaturated group equivalent of 100 to 5000 g / mol.
[0030]
[11] The adhesive composition according to any one of [1] to
[10] , wherein the (meth)acrylic resin (A) has a hydroxyl value of 0.01 to 50 mgKOH / g.
[0031]
[12] A pressure-sensitive adhesive sheet comprising a substrate layer and a pressure-sensitive adhesive layer formed from a thermally cured product or a photothermocured product of the pressure-sensitive adhesive composition according to any one of [1] to
[11] .
[0032]
[13] A dicing tape comprising a substrate layer and an adhesive layer formed from a thermally cured product or a photothermocured product of the adhesive composition according to any one of [1] to
[11] .
[0033]
[14] A dicing die bonding integrated film comprising, in order, a base layer, an adhesive layer formed from a thermally cured product or a photothermocured product of the adhesive composition according to any one of [1] to
[11] , and an adhesive layer.
[0034] Effects of the Invention
[0035] According to the present disclosure, an adhesive composition can be provided, which can provide an adhesive sheet having high adhesive force and excellent water resistance, and whose adhesive force is greatly reduced after irradiation with ultraviolet rays. According to the present disclosure, an adhesive sheet, a dicing tape, and a dicing / chip bonding integrated film having a cured product of the above-mentioned adhesive composition as an adhesive layer can be provided. According to the present disclosure, an adhesive sheet having excellent water resistance and sufficient adhesive force to an adherend, and having excellent peelability after UV irradiation can be provided. In addition, a dicing tape and a dicing / chip bonding integrated film that can suppress the scattering of tiny semiconductor chips and easily pick up semiconductor chips after ultraviolet irradiation can be provided. DETAILED DESCRIPTION
[0036] Hereinafter, embodiments of the present invention will be described in detail. However, the present invention is not limited to the embodiments described below.
[0037] In this specification, when "to" is used for a numerical range, the numerical values at both ends are respectively an upper limit and a lower limit, and are included in the numerical range. When multiple upper limits or lower limits are recorded, the numerical range can be formed by all combinations of the upper limits and lower limits. Similarly, when multiple numerical ranges are recorded, a single numerical range can be formed by selecting upper limits and lower limits from these numerical ranges and combining them.
[0038] In the present specification, “(meth)acrylic” means methacrylic or acrylic, “(meth)acrylate” means acrylate or methacrylate, and “(meth)acryloyloxy” means acryloyloxy or methacryloyloxy.
[0039] In the present specification, the "structural unit" refers to a unit derived from a polymerizable compound used as a monomer or a unit obtained by further modifying a unit derived from a polymerizable compound used as a monomer.
[0040] In the present specification, the term "photo-crosslinkable adhesive" refers to a thermosetting adhesive composition, and has photo-crosslinkability in the state of the thermosetting adhesive. The photo-crosslinkable adhesive can be crosslinked by ultraviolet irradiation.
[0041] In the present specification, the "photothermosetting material" refers to a material obtained by cross-linking the above-mentioned photo-crosslinkable adhesive by ultraviolet irradiation.
[0042] In this specification, the “weight average molecular weight (Mw)” and “number average molecular weight (Mn)” are values measured by gel permeation chromatography (GPC) under the following conditions at room temperature (23° C.) and obtained using a standard polystyrene calibration curve.
[0043] Equipment: Shodex (trademark) GPC-101 (RESONAC Co., Ltd.)
[0044] Column: Shodex (trademark) LF-804 (RESONAC Co., Ltd.)
[0045] Column temperature: 40°C
[0046] Sample: 0.2 mass% tetrahydrofuran solution of the sample
[0047] Flow rate: 1mL / min
[0048] Eluent: Tetrahydrofuran
[0049] Detector: Shodex (trademark) RI-71S (RESONAC Co., Ltd.)
[0050] In this specification, "glass transition temperature (Tg)" refers to the endothermic starting temperature due to glass transition observed by taking 10 mg of a sample and measuring it using a differential scanning calorimeter (DSC) by changing the temperature of the sample from -100°C to 200°C at a heating rate of 10°C / min. When two or more endothermic starting temperatures are observed, Tg is the simple average of the two or more endothermic starting temperatures.
[0051] [Adhesive composition]
[0052] The adhesive composition contains a (meth)acrylic resin (A), a photopolymerization initiator (B), a crosslinking agent (C), and other components added as needed. The adhesive composition containing the (meth)acrylic resin (A) is suitable for use in a removable adhesive sheet, particularly a dicing tape, and a dicing / die bonding integrated film.
[0053] <(Meth)acrylic resin (A)>
[0054] The (meth)acrylic resin (A) is a diblock copolymer composed of an X block and a Y block. The (meth)acrylic resin (A) has at least one structure derived from a (meth)acryloyloxy group. The structural unit ratio (molar ratio) of the X block and the Y block is 40:60 to 95:5. When a raw monomer group containing a monomer that contributes to adhesion and a monomer that contributes to water resistance is subjected to free radical polymerization, the properties of the monomers in the resulting copolymer are averaged, making it difficult to fully utilize the characteristics of each monomer type. In order to better utilize the characteristics of each monomer type, the present inventors have studied copolymers having multiple blocks containing specific structural units. It was found that a diblock copolymer composed of two blocks containing specific structural units can provide an adhesive composition having excellent water resistance and adhesion.
[0055] The ratio of the structural unit of the X block to the total structural unit of the (meth) acrylic resin (A) is 40 mol% or more, preferably 50 mol% or more, and more preferably 55 mol% or more. The ratio of the structural unit of the X block to the total structural unit of the (meth) acrylic resin (A) is 95 mol% or less, preferably 90 mol% or less, and more preferably 85 mol% or less. The combination of these lower limits and upper limits can be any combination. When the structural unit ratio of the X block is 40 mol% or more, sufficient adhesion of the adhesive layer to the adherend can be obtained. Therefore, in the case of being used as a dicing tape or a dicing / chip bonding integrated film, the cutting property is sufficient. When the structural unit ratio of the X block is 95 mol% or less, sufficient water resistance of the adhesive layer to the adherend can be obtained. Therefore, in the case of being used as a dicing tape or a dicing / chip bonding integrated film, sufficient adhesion is used in the process of using water such as cutting water.
[0056] The ratio of the structural unit of the Y block to the total structural unit of the (meth) acrylic resin (A) is 5 mol% or more, preferably 10 mol% or more, and more preferably 15 mol% or more. The ratio of the structural unit of the Y block to the total structural unit of the (meth) acrylic resin (A) is 60 mol% or less, preferably 50 mol% or less, and more preferably 45 mol% or less. The combination of these lower limits and upper limits can be any combination. When the structural unit ratio of the Y block is 5 mol% or more, sufficient water resistance of the adhesive layer to the adherend can be obtained. Therefore, in the case of being used as a dicing tape or a dicing / chip bonding integrated film, sufficient adhesion is used in the process of water such as cutting water. When the structural unit ratio of the Y block is 60 mol% or less, sufficient adhesion of the adhesive layer to the adherend can be obtained. Therefore, in the case of being used as a dicing tape or a dicing / chip bonding integrated film, the cutting property is sufficient.
[0057] The X block includes a structural unit (M-1) (also referred to as structural unit (M-1)) with a hydroxyl group and a structural unit (M-2) (also referred to as structural unit (M-2)) with an ethylenically unsaturated group. The X block also includes other structural units (M-4) (also referred to as structural unit (M-4)) other than the structural unit (M-1) and the structural unit (M-2). When the total of the structural unit of the X block is set to 100 mol%, the total ratio of the structural unit (M-1) with a hydroxyl group and the structural unit (M-2) with an ethylenically unsaturated group included in the X block is 18 mol% or more, preferably 19 mol% or more, more preferably 20 mol% or more. When the total of the structural unit of the X block is set to 100 mol%, the total ratio of the structural unit (M-1) with a hydroxyl group and the structural unit (M-2) with an ethylenically unsaturated group included in the X block is 95 mol% or less, preferably 60 mol% or less, more preferably 40 mol% or less. The combination of these lower limits and upper limits can be any combination.
[0058] The Y block contains as a result of SP value of 20 (J / cm 3 ) 1 / 2The structural unit of the following ethylenically unsaturated compound (m-3) (also referred to as compound (m-3)) and the structural unit (M-3) (also referred to as structural unit (M-3)) having no ethylenically unsaturated group and hydroxyl group. The Y block may contain a structural unit (M-1) having a hydroxyl group, a structural unit (M-2) having an ethylenically unsaturated group, and other structural units (M-5) (also referred to as structural units (M-5) other than structural units (M-3) selected from structural units having a hydroxyl group, and structural units having an ethylenically unsaturated group, as required. When the total of the structural units of the Y block is 100 mol%, the total ratio of the structural unit (M-1) having a hydroxyl group and the structural unit (M-2) having an ethylenically unsaturated group contained in the Y block is 0 mol% or more, 3 mol% or more, or 5 mol% or more. When the total of the structural units of the Y block is regarded as 100 mol%, the total ratio of the structural unit (M-1) having a hydroxyl group and the structural unit (M-2) having an ethylenically unsaturated group contained in the Y block is 17 mol% or less, preferably 15 mol% or less, and more preferably 10 mol% or less. Any combination of these lower limits and upper limits may be used.
[0059] By making the adhesive composition contain (meth) acrylic resin (A), sufficient adhesion to the adherend is obtained mainly through the contribution of the X block, and excellent peelability from the adherend is obtained after UV irradiation. By making the adhesive composition contain (meth) acrylic resin (A), an adhesive sheet with good water resistance is obtained mainly through the contribution of the Y block. Therefore, the adhesive composition containing (meth) acrylic resin (A) is used for the dicing tape of the adhesive layer and the dicing / chip bonding integrated film, and has excellent water resistance in the process using water such as cutting water, good cutting performance, and excellent pickup of the semiconductor chip monolithic after UV irradiation.
[0060] The weight average molecular weight (Mw) of the (meth)acrylic resin (A) is preferably 1×10 4 More preferably 3×10 4 More preferably, 10×10 4 The weight average molecular weight (Mw) of the (meth)acrylic resin (A) is preferably 200×10 4 Below, more preferably 150×10 4 Below, more preferably 100×10 4 The weight average molecular weight (Mw) is 1×10 4 When the above conditions are met, the adhesive sheet obtained by curing the adhesive composition has good adhesive strength, and when the adhesive sheet is used as a dicing tape or a dicing / die bonding integrated film, the dicing property is good. 4When the adhesive layer is below 100%, sufficient peelability can be obtained after UV irradiation, and when the adhesive sheet is used as a dicing tape or a dicing / chip bonding integrated film, good pick-up can be obtained. Moreover, the adhesive layer can be made to obtain sufficient strength, and the contamination of the adherend when the adhesive sheet is peeled off can be prevented. In addition, the viscosity of the adhesive composition can be controlled in an appropriate range, and the operability when it is applied to the substrate and the adhesive sheet is made can be ensured, and a uniform film thickness can be obtained.
[0061] The molecular weight distribution (Mw / Mn) of (meth) acrylic resin (A) can be more than 1.1, more than 1.3, and more than 1.5. The molecular weight distribution (Mw / Mn) of (meth) acrylic resin (A) is preferably less than 5.0, more preferably less than 4.5, and more preferably less than 4.0. The combination of these lower limits and upper limits can be any combination. When the molecular weight distribution is more than 1.1, it is easy to control the manufacturing conditions. When the molecular weight distribution is less than 5.0, compared with the situation of synthesizing by free radical polymerization without controlling the molecular weight distribution, a better adhesive composition can be obtained. That is, by narrowing the molecular weight distribution, on the one hand, the (meth) acrylic resin (A) of the low molecular weight part can be reduced to the cutting property, pick-up property and adherend pollution of the adhesive sheet. On the other hand, the (meth) acrylic resin (A) of the high molecular weight part can be reduced to the viscosity control of the adhesive composition, and the adhesive sheet performance is stably obtained.
[0062] The ethylenically unsaturated group equivalent of (methyl) acrylic resin (A) is preferably more than 100g / mol, more preferably more than 250g / mol, and more preferably more than 500g / mol. The ethylenically unsaturated group equivalent of (methyl) acrylic resin (A) is preferably less than 5000g / mol, more preferably less than 3000g / mol, and more preferably less than 2000g / mol. The combination of these lower limits and upper limits can be any combination. When the ethylenically unsaturated group equivalent of (methyl) acrylic resin (A) is more than 100g / mol, the compatibility with conventional organic solvents becomes better. When the ethylenically unsaturated group equivalent of (methyl) acrylic resin (A) is less than 5000g / mol, the adhesive layer can obtain sufficient peelability after UV irradiation, and when the adhesive sheet is used as a dicing tape or a dicing / chip bonding integrated film, good pickup can be obtained.
[0063] In this specification, the ethylenically unsaturated group equivalent of the (meth)acrylic resin (A) refers to the mass of the (meth)acrylic resin (A) corresponding to 1 mol of ethylenically unsaturated bonds. The ethylenically unsaturated group equivalent of the (meth)acrylic resin (A) in one embodiment is a calculated value calculated from the feed amount assuming that 100% of each raw material used in the manufacture of the (meth)acrylic resin (A) is reacted. The ethylenically unsaturated group equivalent of the (meth)acrylic resin (A) can be calculated from the bonding amount of the halogen and the (meth)acrylic resin (A). The bonding amount of the halogen and the (meth)acrylic resin (A) can be evaluated according to JIS K 0070:1992.
[0064] The glass transition temperature (Tg) of the (meth)acrylic resin (A) is preferably -80°C to 0°C, more preferably -70°C to -10°C, and further preferably -65°C to -20°C. When the glass transition temperature is -80°C or higher, the pickup property is good. When the glass transition temperature is 0°C or lower, the adhesion before UV irradiation is good.
[0065] The hydroxyl value of (meth) acrylic resin (A) is preferably 0.01mgKOH / g or more, more preferably 2.5mgKOH / g or more, and more preferably 5mgKOH / g or more. The hydroxyl value of (meth) acrylic resin (A) is preferably 50mgKOH / g or less, more preferably 30mgKOH / g or less, and more preferably 15mgKOH / g or less. The combination of these lower limits and upper limits can be any combination. When the hydroxyl value of (meth) acrylic resin (A) is 0.01mgKOH / g or more, the resin can be fully heat-cured by a cross-linking reaction based on heating, so the adhesive sheet obtained has good adhesion. Therefore, when the adhesive sheet is used as a dicing tape or a dicing / chip bonding integrated film, the cutting property is good. Moreover, the adhesive layer can be made to obtain sufficient strength, and it is possible to prevent the contamination of the adherend when the adhesive sheet is peeled off. When the hydroxyl value of (meth) acrylic resin (A) is 50mgKOH / g or less, the amount of hydroxyl contained in the adhesive layer after heat curing is fully reduced, so the water resistance of the adhesive sheet obtained is good. Therefore, when the pressure-sensitive adhesive sheet is used as a dicing tape or a dicing die-bonding integrated film, the pressure-sensitive adhesive sheet has excellent water resistance even in a process using water such as cutting water, and the dicing property is improved.
[0066] In this specification, the hydroxyl value of the (meth)acrylic resin (A) is a value measured using a mixed indicator of bromothymol blue and phenol red in accordance with JIS K0070: 1992. The hydroxyl value of a resin refers to the mass (mg) of potassium hydroxide required to neutralize acetic acid bonded to hydroxyl groups when acetylation is performed on 1 g of the resin.
[0067] (X block of (meth)acrylic resin (A))
[0068] The X block of the (meth)acrylic resin (A) comprises a structural unit (M-1) having a hydroxyl group and a structural unit (M-2) having an ethylenically unsaturated group. The X block further comprises another structural unit (M-4) other than the structural unit (M-1) and the structural unit (M-2).
[0069] 《Structural unit having hydroxyl group (M-1)》
[0070] The structural unit (M-1) is a structural unit having a hydroxyl group without an ethylenically unsaturated group. The structural unit (M-1) is preferably a structural unit derived from a compound having a hydroxyl group and a (meth)acryloyloxy group. By making the (meth)acrylic resin (A) have a structural unit (M-1), an adhesive sheet with sufficient adhesive force can be obtained. In addition, the crosslinking point with the crosslinking agent (C) described later can be ensured to improve the strength of the adhesive layer. The structural unit (M-1) can be only one type or two or more types.
[0071] When the total of the structural unit of the X block of (meth) acrylic resin (A) is set to 100 mol%, the content of the structural unit (M-1) in the X block is preferably 0.1 mol% or more, more preferably 1 mol% or more, and more preferably 1.5 mol% or more. When the total of the structural unit of the X block of (meth) acrylic resin (A) is set to 100 mol%, the content of the structural unit (M-1) in the X block is preferably 35 mol% or less, more preferably 20 mol% or less, and more preferably 10 mol% or less. The combination of these lower limits and upper limits can be any combination. When the content of the structural unit (M-1) in the X block is 0.1 mol% or more, by a cross-linking reaction based on heating, the resin can be fully thermoset. In addition, the adhesive force of the obtained adhesive sheet is good, and when the adhesive sheet is used as a dicing tape or a dicing / chip bonding integrated film, the cutting property is good. Moreover, the adhesive layer can be made to obtain sufficient strength, and the contamination of the adherend can be prevented when the adhesive sheet is peeled off. When the content of the structural unit (M-1) in the X block is 35 mol% or less, the amount of hydroxyl groups contained in the adhesive layer after thermal curing is sufficiently reduced, so that the water resistance of the obtained adhesive sheet is good. Therefore, when the adhesive sheet is used as a dicing tape or a dicing / chip bonding integrated film, the adhesive sheet also has excellent water resistance in the process using water such as cutting water, and the cutting property is improved.
[0072] The structural unit (M-1) is a structural unit derived from an ethylenically unsaturated compound (m-1) having a hydroxyl group (also referred to as compound (m-1)). There are no particular restrictions on the ethylenically unsaturated compound (m-1) having a hydroxyl group as long as it is a compound having a hydroxyl group and one ethylenically unsaturated group. Specifically, there can be mentioned hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2,3-dihydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; (meth)acrylates having an aromatic ring and a hydroxyl group such as hydroxyphenyl (meth)acrylate and 2-hydroxy-3-phenoxypropyl (meth)acrylate; hydroxystyrene, etc. Among them, from the viewpoint of curability when combined with a crosslinking agent (C) described later, hydroxyalkyl (meth)acrylates are preferred, hydroxyalkyl (meth)acrylates having a hydroxyalkyl group with 1 to 6 carbon atoms are more preferred, hydroxyalkyl (meth)acrylates having a hydroxyl group at the end of a linear alkyl group are further preferred, and 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate are particularly preferred.
[0073] 《Structural unit having an ethylenically unsaturated group (M-2)》
[0074] The structural unit (M-2) is a structural unit having an ethylenically unsaturated group. The structural unit (M-2) is preferably a structural unit of a compound having an ethylenically unsaturated group other than a (meth) acryloyloxy group, or a (meth) acryloyloxy group, which is described later. The structural unit (M-2) is a (meth) acrylate (m-2) having an ethylenically unsaturated group other than a (meth) acryloyloxy group, or a compound having an ethylenically unsaturated group other than a (meth) acryloyloxy group. By making the (meth) acrylic resin (A) have a structural unit (M-2), after an adhesive sheet having an adhesive layer using the (meth) acrylic resin (A) is pasted to an adherend, the adhesive force is reduced by UV irradiation, and it can be easily peeled off from the adherend. When the adhesive sheet is used as a dicing tape or a dicing / chip bonding integrated film, the cutting property is good, and excellent pickup can be obtained after UV irradiation. The structural unit (M-2) can be only one or more.
[0075] When the total of the structural unit of the X block of (meth) acrylic resin (A) is set to 100 mol%, the content of the structural unit (M-2) in the X block is preferably 1 mol% or more, more preferably 8 mol% or more, and more preferably 15 mol% or more. When the total of the structural unit of the X block of (meth) acrylic resin (A) is set to 100 mol%, the content of the structural unit (M-2) in the X block is preferably 60 mol% or less, more preferably 40 mol% or less, and more preferably 30 mol% or less. The combination of these lower limits and upper limits can be any combination. When the content of the structural unit (M-2) in the X block is 1 mol% or more, sufficient peelability can be obtained after the adhesive sheet is irradiated with ultraviolet rays, and when the adhesive sheet is used as a dicing tape or a dicing / chip bonding integrated film, good pickup can be obtained. When the content of the structural unit (M-2) in the X block is 60 mol% or less, the compatibility with conventional organic solvents becomes better.
[0076] In one embodiment, the structural unit (M-2) is a structural unit derived from a (meth)acrylate (m-2) (also referred to as compound (m-2)) having an ethylenically unsaturated group other than a (meth)acryloyloxy group. As compound (m-2), there can be cited (meth)acrylate alkenyl esters such as vinyl (meth)acrylate, allyl (meth)acrylate, isopropenyl (meth)acrylate, and 2-butenyl (meth)acrylate; (meth)acrylates containing an unsaturated alicyclic skeleton such as dicyclopentenyloxyethyl (meth)acrylate and dicyclopentenyl (meth)acrylate, etc. Among them, from the perspective of reaction control, alkenyl (meth)acrylate is preferred, allyl (meth)acrylate, isopropenyl (meth)acrylate and 2-butenyl (meth)acrylate are more preferred, and isopropenyl (meth)acrylate is further preferred.
[0077] In one embodiment, the structural unit (M-2) is a structural unit formed by adding an isocyanate group of an ethylenically unsaturated compound (a) containing an isocyanate group to the hydroxyl group of a structural unit derived from an ethylenically unsaturated compound (m-1) having a hydroxyl group. The ethylenically unsaturated compound (a) containing an isocyanate group is not particularly limited as long as it is a compound having no hydroxyl group and having one isocyanate group and an ethylenically unsaturated group. Specifically, (meth)acryloyloxyalkyl isocyanates such as 2-isocyanatoethyl (meth)acrylate, 2-isocyanatopropyl (meth)acrylate, 3-isocyanatopropyl (meth)acrylate, 2-isocyanato-1-methylethyl (meth)acrylate, 2-isocyanato-1,1-dimethylethyl (meth)acrylate, and 4-isocyanatocyclohexyl (meth)acrylate; 2-(2-isocyanatoethoxy)ethyl (meth)acrylate; and 1,1-(bis(meth)acryloyloxymethyl)ethyl isocyanate. Among them, from the perspective of ease of synthesis of the (meth)acrylic resin (A), (meth)acryloyloxyalkyl isocyanates are preferred, and 2-(meth)acryloyloxyethyl isocyanate is more preferred.
[0078] In the case of introducing structural unit (M-2) by adding ethylenically unsaturated compounds (a) containing isocyanate groups to a part of the hydroxyl groups of the structural unit of the ethylenically unsaturated compound (m-1) possessed by the (meth) acrylic copolymer, the addition rate of the ethylenically unsaturated compound (a) containing isocyanate groups relative to the mole number of hydroxyl groups is preferably 40 mol% or more, more preferably 60 mol% or more, and more preferably 80 mol% or more. The addition rate of the ethylenically unsaturated compound (a) containing isocyanate groups is preferably 99 mol% or less, more preferably 98 mol% or less, and more preferably 95 mol% or less. The combination of these lower limits and upper limits can be any combination. When the addition rate of the ethylenically unsaturated compound (a) containing isocyanate groups is 40 mol% or more, sufficient releasability can be obtained after irradiating the adhesive sheet with ultraviolet rays, and when the adhesive sheet is used as a dicing tape or a dicing / chip bonding integrated film, good pickup can be obtained. If the addition rate of the ethylenically unsaturated compound (a) containing an isocyanate group is less than 99 mol%, the resin can be fully thermally cured by a cross-linking reaction based on heating. In addition, the adhesive force of the obtained adhesive sheet is good. Therefore, when the adhesive sheet is used as a dicing tape or a dicing / chip bonding integrated film, the cutting property is good. Moreover, the adhesive layer can be made to obtain sufficient strength, and it is possible to prevent the contamination of the adherend when the adhesive sheet is peeled off.
[0079] Other structural units
[0080] The X block of the (meth)acrylic resin (A) further includes a structural unit (M-4) other than the structural unit (M-1) and the structural unit (M-2). The structural unit (M-4) may be one type or two or more types.
[0081] When the total of the structural unit of the X block of (meth) acrylic resin (A) is set to 100 mol%, the content of other structural units (M-4) in the X block is 5 mol% or more, preferably 25 mol% or more, more preferably 50 mol% or more. When the total of the structural unit of the X block of (meth) acrylic resin (A) is set to 100 mol%, the content of other structural units (M-4) in the X block is 82 mol% or less, preferably 78 mol% or less, more preferably 75 mol% or less, more preferably 70 mol% or less. The combination of these lower limits and upper limits can be any combination. When the content of other structural units (M-4) in the X block is 5 mol% or more, the adhesive force of the obtained adhesive sheet is good. Therefore, when the adhesive sheet is used as a dicing tape or a dicing / chip bonding integrated film, the cutting property is good. When the content of other structural units (M-4) in the X block is 82 mol% or less, the (meth)acrylic resin (A) contains sufficient hydroxyl groups and ethylenically unsaturated groups, so that the thermosetting property and the reduction of the adhesive force caused by ultraviolet irradiation are good. Therefore, when the adhesive sheet is used as a dicing tape or a dicing / die bonding integrated film, the dicing property and the pick-up property are improved.
[0082] Examples of compounds providing other structural units (M-4) include monomers other than compounds (m-1) and (m-2) that are copolymerizable with compounds (m-1) and (m-2). Specific examples include alkyl (meth)acrylates; carboxyl group-containing monomers; dienes such as butadiene and dicyclopentadiene; styrenes; unsaturated dicarboxylic acid diesters; and other vinyl compounds.
[0083] Examples of the alkyl (meth)acrylate include linear or branched alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, neopentyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isopentyl (meth)acrylate, and dodecyl (meth)acrylate; and alicyclic alkyl (meth)acrylates such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, ethylcyclohexyl (meth)acrylate, norbornyl (meth)acrylate, dicyclopentyl (meth)acrylate, isobornyl (meth)acrylate, and adamantyl (meth)acrylate. Among these, linear or branched alkyl (meth)acrylates having an alkyl group with 1 to 5 carbon atoms and cyclohexyl (meth)acrylate are preferred from the viewpoint of reactivity, and at least n-butyl (meth)acrylate is more preferably used.
[0084] Examples of carboxyl group-containing monomers include (meth)acrylic acid, crotonic acid, vinylbenzoic acid, unsaturated monobasic acids such as α-halogenated alkyl, alkoxy, halogen, nitro or cyano substituents of acrylic acid, and unsaturated dibasic acids such as itaconic acid. Among them, (meth)acrylic acid is preferred from the perspective of ease of manufacturing the adhesive layer.
[0085] Specific examples of styrenes include styrene and α-, o-, m- or p-alkyl derivatives of styrene.
[0086] Specific examples of the unsaturated dicarboxylic acid diester include diethyl citraconic acid, diethyl maleate, diethyl fumarate, and diethyl itaconate.
[0087] Specific examples of other vinyl compounds include norbornene (bicyclo[2.2.1]hept-2-ene), 5-methylbicyclo[2.2.1]hept-2-ene, 5-ethylbicyclo[2.2.1]hept-2-ene, tetracyclo[4.4.0.1 2,5 .1 7,10 ]Dodec-3-ene, 8-methyltetracyclo[4.4.0.1 2,5 .1 7,10 ] dodec-3-ene, 8-ethyltetracyclo[4.4.0.1 2,5 .1 7,10 ] dodec-3-ene, tricyclo[5.2.1.0 2,6 ]dec-8-ene, tricyclic[5.2.1.0 2,6 ]dec-3-ene, tricyclo[4.4.0.1 2,5 ] undec-3-ene, tricyclo[6.2.1.0 1,8 ]Undec-9-ene, tricyclo[6.2.1.0 1,8]undec-4-ene, tetracyclo[4.4.0.1 2,5 .1 7,10 .0 1 ,6 ]Dodec-3-ene, 8-methyltetracyclo[4.4.0.1 2,5 .1 7,10 .0 1,6 ] dodec-3-ene, 8-ethylenetetracyclo[4.4.0.1 2 ,5 .1 7,10 ] dodec-3-ene, 8-ethylenetetracyclo[4.4.0.1 2,5 .1 7,10 .0 1,6 ] dodec-3-ene, pentacyclic [6.5.1.1 3 ,6 .0 2,7 .0 9,13 ]pentadeca-4-ene, pentacyclo[7.4.0.1 2,5 .1 9,12 .0 8,13 ]pentadeca-3-ene, (methyl)acrylanilide, vinylpyridine, vinyl acetate, etc.
[0088] Among them, from the viewpoint of reaction control, alkyl (meth)acrylates are preferred, and linear or branched alkyl (meth)acrylates having an alkyl group with 1 to 5 carbon atoms are more preferred.
[0089] <Y Block of (Meth)Acrylic Resin (A)>
[0090] The Y block of the (meth)acrylic resin (A) contains an SP value of 20 (J / cm 3 ) 1 / 2 The Y block may contain other structural units other than the structural unit (M-3) selected from the structural unit (M-1) having a hydroxyl group, the structural unit (M-2) having an ethylenically unsaturated group, and other structural units (M-5) other than the structural units (M-1) to (M-3), as required.
[0091] 《The SP value is 20(J / cm 3 ) 1 / 2 The following structural unit (M-3) of the ethylenically unsaturated compound (m-3)
[0092] The structural unit (M-3) is a structural unit having no ethylenically unsaturated group and no hydroxyl group and having an SP value of 20 (J / cm 3 ) 1 / 2The structural unit (M-3) is preferably derived from an ethylenically unsaturated compound (m-3) having an SP value of 20 (J / cm 3 ) 1 / 2 The following structural units of compounds having a (meth)acryloyloxy group: The structural unit (M-3) may be one type or two or more types.
[0093] In this specification, the SP value refers to the solubility parameter value (δTot) calculated using a program such as HSPiP (Hansen Solubility Parameters in Practice). δTot represents the magnitude of the HSP vector. By making the (meth)acrylic resin (A) contain the structural unit (M-3), a PSA sheet with good water resistance can be obtained.
[0094] When the total of the structural unit of the Y block of (meth) acrylic resin (A) is set to 100 mol%, the content of structural unit (M-3) in Y block can be more than 50 mol%, can be more than 60 mol%, can be more than 70 mol%, can be more than 80 mol%. The total of the structural unit of the Y block of (meth) acrylic resin (A) is regarded as 100 mol%, and the content of structural unit (M-3) in Y block can be less than 80 mol%, can be less than 90 mol%, can be less than 100 mol%. The combination of these lower limits and upper limits can be any combination. From the water resistance of the adhesive composition, the content of the structural unit (M-3) in Y block is preferably 100 mol%. When the content of structural unit (M-3) is more than 50 mol%, the hydrophobicity of the Y block of (meth) acrylic resin (A) is good, so the water resistance of the adhesive sheet obtained becomes better. Therefore, when the adhesive sheet is used as a dicing tape or a dicing / chip bonding integrated film, the adhesive sheet also has excellent water resistance in the process using water such as cutting water, and the cutting property is improved. When the content of the structural unit (M-3) is within the above range, the Tg of the Y block of the (meth)acrylic resin (A) can be adjusted to an appropriate range, and the adhesive force can be improved.
[0095] Specific examples of the compound (m-3) providing the structural unit (M-3) include alkyl (meth)acrylates and styrenes. Examples of the alkyl (meth)acrylates include linear or branched alkyl (meth)acrylates having an alkyl group having 1 to 5 carbon atoms, such as methyl (meth)acrylate (18.8, 18.0) and n-butyl (meth)acrylate (19.0, 17.1), linear or branched alkyl (meth)acrylates having an alkyl group having 6 to 30 carbon atoms, such as stearyl (meth)acrylate (16.3, 16.3) and isostearyl (meth)acrylate (16.1, 16.1), and alkyl (meth)acrylates having 6 to 30 carbon atoms, such as stearyl (meth)acrylate (16.3, 16.3) and isostearyl (meth)acrylate (16.1, 16.1). ) cyclopentyl (18.0, 17.6), (meth) acrylate cyclohexyl (18.0, 17.7), (meth) acrylate ethyl cyclohexyl (18.2, 17.6), (meth) acrylate norbornyl (18.3, 18.0), (meth) acrylate dicyclopentyl (17.6, 17.5), (meth) acrylate isobornyl (17.1, 17.0), (meth) acrylate adamantyl (17.7, 17.5) and other alicyclic skeleton containing (meth) acrylate. It should be noted that the numerical value after each compound name is recorded in the order of acrylate, methacrylate, SP value ((J / cm 3 ) 1 / 2 Specific examples of styrenes include styrene (18.3); alkyl derivatives of styrene such as α-methylstyrene (17.8), o-methylstyrene (18.3), m-methylstyrene (18.2), and p-methylstyrene (18.6). It should be noted that the numerical value after each compound name is the SP value ((J / cm 3 ) 1 / 2 ). Among them, from the viewpoint of reaction control and SP value, it is preferably selected from at least one of a linear or branched (meth) alkyl acrylate having an alkyl group with 6 to 30 carbon atoms, a (meth) acrylate containing an alicyclic skeleton, and styrene, more preferably selected from at least one of n-butyl acrylate, cyclohexyl acrylate, isostearyl acrylate, and styrene, further preferably selected from at least one of isostearyl acrylate and styrene, and particularly preferably styrene. Compound (m-3) may be used alone or in combination of two or more.
[0096] 《Structural Unit (M-5)》
[0097] When the total of the structural unit of the Y block of (meth) acrylic resin (A) is set to 100 mol%, the content of the structural unit (M-5) in the Y block can be 5 mol% or more, or 10 mol% or more, or 15 mol% or more. When the total of the structural unit of the Y block of (meth) acrylic resin (A) is set to 100 mol%, the content of the structural unit (M-5) in the Y block is preferably 50 mol% or less, more preferably 40 mol% or less, and further preferably 20 mol% or less. The combination of these lower limits and upper limits can be any combination. When the content of the structural unit (M-5) in the Y block is 5 mol% or more, the Tg of the Y block of the (meth) acrylic resin (A) can be adjusted to an appropriate range, and the bonding force can be improved. When the content of the structural unit (M-5) in the Y block is 50 mol% or less, the hydrophobicity of the Y block of the (meth) acrylic resin (A) is good, so the water resistance of the adhesive sheet obtained becomes better. Therefore, when the adhesive sheet is used as a dicing tape or a dicing / chip bonding integrated film, the adhesive sheet also has excellent water resistance in the process of using water such as cutting water, and the cutting property becomes better. From the aspect of water resistance, the Y block preferably does not include the structural unit (M-5). The structural unit (M-5) can be only one or more than two.
[0098] Examples of the compound providing the structural unit (M-5) include compounds other than the compounds (m-1) and (m-2) copolymerizable with the compound (m-3) and having an SP value exceeding 20 (J / cm 3 ) 1 / 2 Specific examples include carboxyl group-containing monomers; unsaturated dicarboxylic acid diesters; other vinyl compounds, etc.
[0099] Examples of carboxyl group-containing monomers include methacrylic acid, crotonic acid, unsaturated monobasic acids such as alkyl halide, alkoxy, halogen, nitro or cyano substituents of acrylic acid at the α-position, and unsaturated dibasic acids such as itaconic acid. Among them, methacrylic acid is preferred from the viewpoint of ease of production of the adhesive layer.
[0100] Specific examples of the unsaturated dicarboxylic acid diester include diethyl citraconic acid, diethyl maleate, diethyl fumarate, and diethyl itaconate.
[0101] Specific examples of other vinyl compounds include (meth)acrylanilide and the like.
[0102] Among them, from the perspective of reaction control, it is preferred that the SP value exceeds 20 (J / cm 3 ) 1 / 2 Carboxyl-containing monomers.
[0103] The (meth)acrylic resin (A) may contain at least one selected from the structural unit (M-1) and the structural unit (M-2) in the Y block within a range not impairing the effect. Specific examples and preferred examples of the structural units (M-1) and (M-2) contained in the Y block are the same as those of the structural units (M-1) and (M-2) contained in the X block.
[0104] In the case where the Y block includes a structural unit (M-1), when the total of the structural unit of the Y block of the (meth) acrylic resin (A) is set to 100 mol%, the content of the structural unit (M-1) in the Y block can be 1 mol% or more, or 2 mol% or more, or 5 mol% or more. When the Y block includes a structural unit (M-1), when the total of the structural unit of the Y block of the (meth) acrylic resin (A) is set to 100 mol%, from the perspective of improving the water resistance as an adhesive sheet, it is preferably 15 mol% or less, more preferably 10 mol% or less, and further preferably 5 mol% or less. The combination of these lower limits and upper limits can be any combination.
[0105] In the case where the Y block of (meth) acrylic resin (A) includes structural unit (M-1), by a cross-linking reaction based on heating, the resin can be fully heat-cured. The adhesive force of the adhesive sheet obtained is also good, and when the adhesive sheet is used as a dicing tape or a dicing / chip bonding integrated film, the cutting property is good. Moreover, the adhesive layer can be made to obtain sufficient strength, and the contamination of the adherend can be prevented when the adhesive sheet is peeled off. On the other hand, from the aspect of improving water resistance, it is preferred that (meth) acrylic resin (A) does not include structural unit (M-1) in the Y block.
[0106] In the case where the Y block of (meth) acrylic resin (A) includes structural unit (M-2), when the total of the structural unit of the Y block of (meth) acrylic resin (A) is set to 100 mol%, the content of structural unit (M-2) in Y block can be more than 1 mol%, can also be more than 2 mol%, can also be more than 5 mol%. When the total of the structural unit of the Y block of (meth) acrylic resin (A) is set to 100 mol%, when Y block includes structural unit (M-2), the content of structural unit (M-2) in Y block is preferably less than 15 mol%, more preferably less than 10 mol%, more preferably less than 5 mol%. The combination of these lower limits and upper limits can be any combination. In the case where the Y block of (meth) acrylic resin (A) includes structural unit (M-2), after the adhesive sheet with the adhesive layer using it is pasted on the adherend, the adhesive force is reduced by UV irradiation, and it can be easily peeled off from the adherend. When used as a dicing tape or a dicing / die bonding integrated film, excellent pick-up properties can be obtained after UV irradiation. On the other hand, from the perspective of improving water resistance, it is preferred that the (meth)acrylic resin (A) does not have the structural unit (M-2) in the Y block.
[0107] <Photopolymerization Initiator (B)>
[0108] Examples of the photopolymerization initiator (B) include benzophenone, benzil, benzoin, ω-bromoacetophenone, chloroacetone, acetophenone, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, p-dimethylaminoacetophenone, p-dimethylaminoacetophenone, 2-chlorobenzophenone, 4,4'-dichlorobenzophenone, 4,4'-bisdiethylaminobenzophenone, Michler's ketone, benzoin methyl ether, benzoin Carbonyl photopolymerization initiators include isobutyl ether, benzoin n-butyl ether, benzyl methyl ketal, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropane-1-one, methyl benzoylformate, 4'-dimethylaminoacetophenone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one and the like.
[0109] Examples of the photopolymerization initiator (B) include sulfide-based photopolymerization initiators such as diphenyl disulfide, dibenzyl disulfide, tetraethylthiuram disulfide, and tetramethylammonium monosulfide; acylphosphine oxides such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide and 2,4,6-trimethylbenzoylphenylethoxyphosphine oxide; quinone-based photopolymerization initiators such as benzoquinone and anthraquinone; sulfonyl chloride-based photopolymerization initiators; and thioxanthone-based photopolymerization initiators such as thioxanthone, 2-chlorothioxanthone, and 2-methylthioxanthone.
[0110] Among these photopolymerization initiators (B), carbonyl photopolymerization initiators and acylphosphine oxides are preferred from the viewpoint of solubility in the adhesive composition, and at least one selected from 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyldiphenylphosphine oxide is more preferred.
[0111] The photopolymerization initiator (B) may be used alone or in combination of two or more.
[0112] The photopolymerization initiator (B) is preferably 0.1 to 5.0 parts by mass, and more preferably 0.3 to 2.0 parts by mass, relative to 100 parts by mass of the (meth)acrylic resin (A). When the content of the photopolymerization initiator (B) relative to 100 parts by mass of the (meth)acrylic resin (A) is 0.1 parts by mass or more, the crosslinking density of the photocrosslinkable adhesive (i.e., the thermosetting product of the adhesive composition) can be increased at a sufficiently fast curing speed during UV irradiation. Therefore, when the photocrosslinkable adhesive is used for the adhesive layer, the adhesive force of the adhesive layer after UV irradiation can be sufficiently reduced. When the content of the photopolymerization initiator (B) relative to 100 parts by mass of the (meth)acrylic resin (A) is 5.0 parts by mass or less, the adhesive force and water resistance of the adhesive layer before UV irradiation can be fully maintained. Even if the content of the photopolymerization initiator (B) exceeds 5.0 parts by mass based on 100 parts by mass of the (meth)acrylic resin (A), no effect commensurate with the content of the photopolymerization initiator (B) is observed. Therefore, by setting the content to 5.0 parts by mass or less, the pressure-sensitive adhesive composition can be produced economically.
[0113] <Crosslinking agent (C)>
[0114] The crosslinking agent (C) is a compound having no ethylenically unsaturated bond and having two or more functional groups that react with the hydroxyl groups contained in the (meth) acrylic resin (A). The adhesive composition is cured by heating to allow the functional groups of the crosslinking agent (C) to react with the hydroxyl groups of the (meth) acrylic resin (A), thereby obtaining a photo-crosslinkable adhesive. When the photo-crosslinkable adhesive is used for the adhesive layer, an adhesive sheet having a good balance between the adhesive strength before UV irradiation and the adhesive strength after UV irradiation can be obtained.
[0115] Examples of the functional group reactive with a hydroxyl group possessed by the crosslinking agent (C) include an isocyanate group, an epoxy group, a carboxyl group, an acid anhydride group, and an aziridine group. From the viewpoint of reactivity, an isocyanate group and an epoxy group are preferred, and an isocyanate group is particularly preferred.
[0116] Examples of the crosslinking agent (C) include 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hydrogenated toluene diisocyanate, 1,3-xylylene diisocyanate, 1,4-xylylene diisocyanate, diphenylmethane-4,4′-diisocyanate, isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, isocyanurate of hexamethylene diisocyanate, tetramethylxylylene diisocyanate, 1,5-naphthalene diisocyanate, toluene diisocyanate of trimethylolpropane, and the like. ester adducts, trimethylolpropane xylylene diisocyanate adducts, triphenylmethane triisocyanate, methylenebis(4-phenylmethane) triisocyanate and other polyisocyanates; 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, bisphenol A-epichlorohydrin type epoxy resins, N,N'-[1,3-phenylenebis(methylene)]bis[bis(oxiran-2-ylmethyl)amine], ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, Polyepoxides such as 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether; melamine compounds such as hexamethoxymethyl melamine, hexaethoxymethyl melamine, hexapropoxymethyl melamine, hexabutoxymethyl melamine, hexapentoxymethyl melamine, hexahexyloxymethyl melamine; ethylene glycol-bis-[3-(2-aziridinyl) propionate], trimethylolpropane- Aziridinyl compounds such as tris[3-(2-aziridinyl)propionate], trimethylolpropane-tris[3-(1-aziridinyl)propionate], trimethylolpropane-tris[3-(2-methyl-1-aziridinyl)propionate], tetramethylolmethane-tris[3-(2-aziridinyl)propionate], pentaerythritol-tris[3-(1-aziridinyl)propionate], N,N'-diphenylmethane-4,4'-bis(1-aziridinylcarboxamide), and N,N'-hexamethylene-1,6-bis(1-aziridinylcarboxamide) are also included.
[0117] Among these crosslinking agents (C), at least one selected from polyisocyanates and polyepoxy compounds is preferably used, and polyisocyanates are more preferably used, because of good reactivity with the (meth)acrylic resin (A).
[0118] The cross-linking agent (C) may be used alone or in combination of two or more.
[0119] Relative to 100 parts by mass of (meth) acrylic resin (A), the crosslinking agent (C) is preferably 0.1 to 30 parts by mass, more preferably 0.1 to 20 parts by mass, further preferably 0.1 to 10 parts by mass, and further preferably 0.1 to 5 parts by mass. If the content of the crosslinking agent (C) relative to 100 parts by mass of (meth) acrylic resin (A) is 0.1 parts by mass or more, a three-dimensional crosslinked structure is fully formed in the photo-crosslinkable adhesive during UV irradiation. Therefore, in the case where a photo-crosslinkable adhesive is used for an adhesive, the adhesive force of the adhesive after UV irradiation can be fully reduced. If the content of the crosslinking agent (C) relative to 100 parts by mass of (meth) acrylic resin (A) is 30 parts by mass or less, the balance between the properties of the photo-crosslinkable adhesive and the cured product after UV irradiation is good, and when used as a dicing tape or a dicing / chip bonding integrated film, it shows good adhesion and water resistance. In the case where a photo-crosslinkable adhesive is used for an adhesive, the adhesive force of the adhesive before UV irradiation is good.
[0120] <Other ingredients>
[0121] The pressure-sensitive adhesive composition may contain other components in addition to the (meth)acrylic resin (A), the photopolymerization initiator (B) and the crosslinking agent (C) as necessary. Examples of other components include a tackifier, a solvent and various additives.
[0122] (Thickener)
[0123] As the tackifier, any known tackifier can be used without particular limitation. Examples of the tackifier include terpene tackifier resins, phenolic tackifier resins, rosin tackifier resins, aliphatic petroleum resins, aromatic petroleum resins, copolymeric petroleum resins, alicyclic petroleum resins, xylene resins, epoxy tackifier resins, polyamide tackifier resins, ketone tackifier resins, and elastomer tackifier resins. These tackifiers can be used alone or in combination of two or more.
[0124] When a tackifier is used, the content of the tackifier in the pressure-sensitive adhesive composition is preferably 30 parts by mass or less, more preferably 5 to 20 parts by mass, based on 100 parts by mass of the (meth)acrylic resin (A).
[0125] (Solvent)
[0126] The solvent can be used to dilute the adhesive composition for the purpose of adjusting the viscosity of the adhesive composition. For example, when applying the adhesive composition, the solvent can be used to make the viscosity of the adhesive composition appropriate. As the solvent, the solvent used when synthesizing the (meth) acrylic resin (A) can be directly used, or a solvent can be further added to the solvent.
[0127] As the solvent, for example, organic solvents such as methyl ethyl ketone, methyl isobutyl ketone, acetone, ethyl acetate, propyl acetate, butyl acetate, tetrahydrofuran, dioxane, cyclohexanone, hexane, toluene, xylene, n-propanol, and isopropanol can be used. These solvents can be used alone or in combination of two or more.
[0128] (additive)
[0129] Examples of the additives include plasticizers, surface lubricants, leveling agents, softeners, antioxidants, anti-aging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, light stabilizers such as benzotriazoles, phosphates and other flame retardants, surfactants, and antistatic agents.
[0130] [Method for producing (meth)acrylic resin (A)]
[0131] For (meth) acrylic resin (A), for example, it can be manufactured by the following method, which includes a step (i-1) of polymerizing the raw monomer group (mX) constituting the X block by reversible addition-fragmentation chain transfer (RAFT: Reversible Addition-Fragmentation chain Transfer), a step (i-2) of polymerizing the raw monomer group (mY) constituting the Y block by reversible addition-fragmentation chain transfer (RAFT: Reversible Addition-Fragmentation chain Transfer), and a step (ii) of introducing an ethylenically unsaturated group by adding an ethylenically unsaturated compound having a functional group such as an isocyanate group to a part of the hydroxyl groups of the copolymer obtained by the steps (i-1) and (i-2) as needed. The order of the steps (i-1) and (i-2) for synthesizing each block is not particularly limited, and it is preferred that the step (i-2) is performed before the step (i-1). Below, exemplary embodiments of the steps (i-1), (i-2) and (ii) are described.
[0132] <Step (i-1)>
[0133] Step (i-1) is a step of RAFT polymerization of a raw monomer group (mX) in the presence of a reversible addition-fragmentation chain transfer agent (RAFT agent), wherein the raw monomer group (mX) comprises an ethylenically unsaturated compound (m-1) having a hydroxyl group, an optional (meth)acrylate (m-2) having an ethylenically unsaturated group other than a (meth)acryloyloxy group, and optional other monomers other than compounds (m-1) and (m-2). In this specification, RAFT polymerization refers to free radical polymerization carried out in the presence of a RAFT agent. RAFT polymerization is a type of active free radical polymerization. Active free radical polymerization is generally known as a polymerization method that can obtain a polymer with a small molecular weight distribution, and as specific examples thereof, atom transfer radical polymerization, organic tellurium-mediated free radical polymerization, RAFT polymerization, etc. can be cited. Among them, RAFT polymerization is suitable for adhesive applications.
[0134] The weight average molecular weight of each block obtained by steps (i-1) and (i-2) can be controlled, for example, by adjusting the amount of free radical polymerization initiator and RAFT agent used. By controlling the weight average molecular weight of each block, the structural unit ratio (molar ratio) of the X block and the Y block can be controlled within a desired range.
[0135] The reaction temperature can be appropriately set according to the type of free radical polymerization initiator used, etc. The reaction temperature is preferably 40 to 125° C., more preferably 60 to 120° C. The reaction time can be appropriately set according to the type of free radical polymerization initiator used, etc. The reaction time is preferably 5 to 24 hours, more preferably 10 to 15 hours.
[0136] As the polymerization method, solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, alternating copolymerization, etc. can be used. Among these polymerization methods, considering the addition reaction in step (ii), solution polymerization is preferably used in view of the ease of reaction.
[0137] From the perspective of the polymerization rate of the raw monomer group (mX), the total concentration of the components other than the solvent in the solution polymerization is preferably 30 to 90% by mass, and more preferably 50 to 80% by mass. Since steps (i-1) and (i-2) are RAFT polymerizations, polymerization is carried out by equilibrium reaction. Therefore, the polymerization is carried out very gently and can be polymerized at a high concentration.
[0138] (Reversible addition fragmentation chain transfer agent (RAFT agent))
[0139] As RAFT agent, as long as it is a type of RAFT agent that polymerizes in one direction with thiocarbonylthio as starting point, known RAFT agent can be used without particular limitation. As RAFT agent, for example, trithiocarbonate, dithioester, dithiocarbonate and dithiocarbamate can be cited. When polymerization is carried out in the presence of these RAFT agents, free radical species chain reaction occurs between the sulfur atom in the RAFT agent and the carbon atom adjacent to the sulfur atom, while polymerization is carried out. Among them, trithiocarbonate is preferred, from the aspect that the reaction speed and reactivity of polymerization are increased and the molecular weight distribution is easily narrowed depending on the size of the transfer constant. It should be noted that, for bilaterally symmetrical trithiocarbonates, the polymer extends in two directions starting from the trithiocarbonate site. Therefore, when polymerization is carried out in the order of step (i-1) and step (i-2), an XYX type triblock copolymer is formed, and when polymerization is carried out in the order of step (i-2) and step (i-1), a YXY type triblock copolymer is formed, and therefore it cannot be used.
[0140] Specific examples of the RAFT agent include sulfur compounds (trithiocarbonates, dithioesters, dithiocarbonates, and dithiocarbamates) represented by the following formula (1), formula (2), formula (3), or formula (4).
[0141] 《Trithiocarbonate》
[0142]
[0143] In formula (1), R 1a and R 1b Each independently represents a hydrogen atom, a hydrocarbon group, a carboxyl group, or a cyano group, and R 1c represents a cyano group, a saturated or unsaturated aliphatic hydrocarbon group which may be substituted with a cyano group or a carboxyl group, or a phenyl group which may be substituted, R 2 represents a saturated or unsaturated aliphatic hydrocarbon group, a part of the hydrogen atoms of which may be substituted by a carboxyl group, or a benzyl group, a part of the hydrogen atoms of which may be substituted by a substituted carbamoyl group, an alkoxycarbonyl group having 2 to 5 carbon atoms which may be substituted by a hydroxyl group, or an alkenyloxycarbonyl group having 3 to 5 carbon atoms, but (R 1a )(R 1b )(R 1c )C and R 2 different.
[0144] Dithioesters
[0145]
[0146] In formula (2), R 3a and R 3b Each independently represents a hydrogen atom, a hydrocarbon group, or a cyano group, R3c represents a carboxyl group, an acetoxymethyl group, or a hydrocarbon group which may be substituted by a cyano group or a carboxyl group, R 4 It represents a hydrocarbon group.
[0147] Dithiocarbonates
[0148]
[0149] In formula (3), R 5a and R 5b Each independently represents a hydrogen atom, a hydrocarbon group, a carboxyl group which may be substituted with a saturated aliphatic hydrocarbon group having 1 to 3 carbon atoms, or a cyano group, and R 5c represents a hydrocarbon group which may be substituted by an alkoxy group, R 6 It represents a hydrocarbon group.
[0150] Dithiocarbamates
[0151]
[0152] In formula (4), R 7a and R 7b Each independently represents a hydrogen atom or a hydrocarbon group, R 7c Represents cyano, R 8 and R 9 Each independently represents a hydrocarbon group, or R 8 and R 9 They may be bonded to form a saturated aliphatic hydrocarbon group having 1 to 3 carbon atoms or a pyrazole ring which may be substituted with a chlorine atom.
[0153] In formula (1), as R 1a and R 1b The hydrocarbon group represented by may be, for example, a straight chain, branched chain or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, among which a straight chain, branched chain or cyclic saturated or unsaturated hydrocarbon group having 1 to 12 carbon atoms is preferred. Examples of the above-mentioned hydrocarbon group include, for example, a straight chain, branched chain or cyclic saturated aliphatic hydrocarbon group having 1 to 20 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, cyclohexyl, undecyl, dodecyl, octadecyl, etc.; an aryl group having 6 to 12 carbon atoms, such as phenyl; an arylalkyl group having 7 to 10 carbon atoms, such as benzyl and phenethyl, etc. In formula (1), R 1cThe saturated or unsaturated aliphatic hydrocarbon group represented by , for example, a linear, branched or cyclic saturated or unsaturated aliphatic hydrocarbon group having 1 to 20 carbon atoms, preferably a linear, branched or cyclic saturated or unsaturated aliphatic hydrocarbon group having 1 to 12 carbon atoms. Examples of the aliphatic hydrocarbon group include a linear, branched or cyclic saturated aliphatic hydrocarbon group having 1 to 20 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, cyclohexyl, undecyl, dodecyl, octadecyl, etc. In formula (1), R 1c For example, 1 to 3 hydrogen atoms of the saturated or unsaturated aliphatic hydrocarbon group represented by may be substituted by a carboxyl group or a cyano group, and the carboxyl group may be further substituted by a saturated aliphatic hydrocarbon group having 1 to 3 carbon atoms. 1c The substituents of the phenyl group which may be substituted as represented by , include substituted carbamoyl, alkoxycarbonyl having 2 to 5 carbon atoms which may be substituted with a hydroxyl group, alkenyloxycarbonyl having 3 to 5 carbon atoms, etc. As the substituents of the substituted carbamoyl group, saturated aliphatic hydrocarbon group having 1 to 3 carbon atoms which may be substituted with a hydroxyl group or an acetoxy group, etc. are mentioned. In formula (1), R 2 The saturated or unsaturated aliphatic hydrocarbon group represented by , for example, a straight chain, branched chain or cyclic saturated or unsaturated aliphatic hydrocarbon group having 1 to 20 carbon atoms, among which an aliphatic hydrocarbon group having 1 to 12 carbon atoms is preferred. Examples of the aliphatic hydrocarbon group include a straight chain, branched chain or cyclic saturated aliphatic hydrocarbon group having 1 to 20 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, cyclohexyl, dodecyl, octadecyl, etc. In formula (1), R 2 For example, 1 to 3 hydrogen atoms of the saturated or unsaturated aliphatic hydrocarbon group represented by may be substituted with carboxyl groups. 2 The substituent of the benzyl group which may be substituted, that is, the substituent of the substituted carbamoyl group, includes a saturated aliphatic hydrocarbon group having 1 to 3 carbon atoms which may be substituted with a hydroxyl group or an acetoxy group. 1a and R 1b are each independently a hydrogen atom, a hydrocarbon group having 1 to 4 carbon atoms, a carboxyl group, or a cyano group, and R 1c is an undecyl group, a hydrocarbon group having 1 to 4 carbon atoms which may be substituted with a carboxyl group, or a phenyl group which may be substituted, R 2 The compound represented by the formula (1) is a linear, branched or cyclic, saturated or unsaturated aliphatic hydrocarbon group having 1 to 20 carbon atoms, or a benzyl group which may be substituted, and R is more preferably 1a and R 1b is a hydrogen atom, a combination of a methyl group or an ethyl group and a cyano group or a carboxyl group, or a hydrogen atom, R 1cis methyl, ethyl, undecyl, or phenyl which may be substituted, R 2 A compound represented by formula (1) which is a straight-chain saturated aliphatic hydrocarbon group having 1 to 20 carbon atoms, or a benzyl group, wherein a part of the hydrogen atoms of the benzyl group may be substituted with a substituted carbamoyl group, an alkoxycarbonyl group having 2 to 5 carbon atoms which may be substituted with a hydroxy group, or an alkenyloxycarbonyl group having 3 to 5 carbon atoms.
[0154] In formula (2), as R 3a , R 3b , R 3c and R 4 The hydrocarbon group represented by may be, for example, a straight chain, branched chain or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, among which a straight chain, branched chain or cyclic saturated or unsaturated hydrocarbon group having 1 to 12 carbon atoms is preferred. Examples of the above-mentioned hydrocarbon group include, for example, a straight chain, branched chain or cyclic saturated aliphatic hydrocarbon group having 1 to 20 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, cyclohexyl, dodecyl, octadecyl, etc.; an aryl group having 6 to 12 carbon atoms, such as phenyl; an arylalkyl group having 7 to 10 carbon atoms, such as benzyl, phenethyl, etc. In formula (2), R 3c The hydrocarbon group which may be substituted with a cyano group or a carboxyl group as represented by may include, for example, a group in which 1 to 3 hydrogen atoms possessed by the above hydrocarbon group are substituted with a cyano group or a carboxyl group. 3a and R 3b are each independently a linear saturated hydrocarbon group having 1 to 4 carbon atoms, R 3c is an aryl group, R 4 The compound represented by formula (2) is an aryl group or a benzyl group, and more preferably R 3a and R 3b are each independently methyl or ethyl, R 3c Phenyl, R 4 A compound represented by formula (2) which is a phenyl group or a benzyl group.
[0155] In formula (3), as R 5a , R 5b , R 5c and R 6 The hydrocarbon group represented by may be, for example, a straight chain, branched chain or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, among which a straight chain, branched chain or cyclic saturated or unsaturated hydrocarbon group having 1 to 12 carbon atoms is preferred. Examples of the above-mentioned hydrocarbon group include, for example, a straight chain, branched chain or cyclic saturated aliphatic hydrocarbon group having 1 to 20 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, cyclohexyl, dodecyl, octadecyl, etc.; an aryl group having 6 to 12 carbon atoms, such as phenyl; an arylalkyl group having 7 to 10 carbon atoms, such as benzyl, phenethyl, etc. In formula (3), R5c Examples of the hydrocarbon group which may be substituted with an alkoxy group include groups in which 1 to 3 hydrogen atoms possessed by the above hydrocarbon groups are substituted with an alkoxy group.
[0156] In formula (4), as R 7a , R 7b , R 8 and R 9 The hydrocarbon group represented by may be, for example, a straight chain, branched chain or cyclic saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, among which a straight chain, branched chain or cyclic saturated or unsaturated hydrocarbon group having 1 to 12 carbon atoms is preferred. Examples of the above-mentioned hydrocarbon group include, for example, a straight chain, branched chain or cyclic saturated aliphatic hydrocarbon group having 1 to 20 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, cyclohexyl, dodecyl, octadecyl, etc.; an aryl group having 6 to 12 carbon atoms, such as phenyl; an arylalkyl group having 7 to 10 carbon atoms, such as benzyl, phenethyl, etc. 8 and R 9 Together with the nitrogen atom of formula (4), they may form a pyrazole ring. The pyrazole ring may be substituted with a saturated aliphatic hydrocarbon group having 1 to 3 carbon atoms or a chlorine atom.
[0157] Many RAFT agents are commercially available. Those that are not commercially available can be readily synthesized by known or customary methods.
[0158] Specific examples of the RAFT agent include trithiocarbonates such as S-cyanomethyl-S-dodecyl trithiocarbonate, 2-[(dodecylsulfanylthiocarbonyl)sulfanyl]propionic acid, 2-{[(2-carboxyethyl)sulfanylthiocarbonyl]sulfanyl}propionic acid, 4-[(2-carboxyethylsulfanylthiocarbonyl)sulfanyl]-4-cyanovaleric acid, 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid, 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid, methyl 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoate, 2-cyano-2-propyldodecyl trithiocarbonate, and benzyl dodecyl trithiocarbonate; and trithiocarbonates such as cyanoethyl dithiopropionate, benzyl dithiopropionate, benzyl dithiobenzoate, acetoxyethyl dithiobenzoate, 2-phenyl-2-propyl dithiobenzoic acid, 2-cyano dithioesters such as -2-propyl dithiobenzoic acid, 4-cyano-4-(phenylthiocarbonylthio)pentanoic acid, and S-(thiobenzoyl)thioglycolic acid; dithiocarbonates such as ethyl 2-[(ethoxythiocarbonyl)thio]propionate, S-(2-propoxyethyl) dithiocarbonate O-ethyl ester, and S-(1-cyano-1-methylethyl) dithiocarbonate O-ethyl ester; dithiocarbamates such as 2-cyano-2-propyl diethyl dithiocarbamate, 2'-cyanobutane-2'-yl 4-chloro-3,5-dimethylpyrazole-1-dithiocarbamate, 2'-cyanobutane-2'-yl 3,5-dimethylpyrazole-1-dithiocarbamate, cyanomethyl 3,5-dimethylpyrazole-1-dithiocarbamate, and cyanomethyl N-methyl-N-phenyl dithiocarbamate. Among them, from the viewpoint of the ease of polymerization of the (meth)acrylic resin (A), trithiocarbonates and dithioesters are preferred, and 2-[(dodecylsulfanylthiocarbonyl)sulfanyl]propionic acid, 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid, 2-{[(2-carboxyethyl)sulfanylthiocarbonyl]sulfanyl}propionic acid, benzyl dodecyl trithiocarbonate and 2-phenyl-2-propyldithiobenzoic acid are more preferred.
[0159] The RAFT agent may be used alone or in combination of two or more.
[0160] When step (i-2) is performed before step (i-1), by continuing to use the RAFT agent blended in step (i-2), a diblock copolymer in which a block synthesized from the raw material monomer group (mX) and a block synthesized from the raw material monomer group (mY) are connected can be obtained.
[0161] The amount of the RAFT agent used is preferably 0.001 to 1.0 parts by mass, more preferably 0.005 to 0.5 parts by mass, and further preferably 0.01 to 0.35 parts by mass relative to a total of 100 parts by mass of the raw material monomer group (mX), the raw material monomer group (mY), and the optionally used ethylenically unsaturated compound having a functional group such as an isocyanate group. If it is 0.001 parts by mass or more, polymerization can be carried out with an effective reaction time. If it is 1.0 parts by mass or less, a sufficiently high molecular weight block can be obtained.
[0162] (Free Radical Polymerization Initiator)
[0163] RAFT polymerization is preferably carried out in the presence of a free radical polymerization initiator. Examples of the free radical polymerization initiator include conventional organic free radical polymerization initiators, and specifically, examples thereof include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2,4,4-trimethylpentane), Azo polymerization initiators such as dimethyl-2,2'-azobis(2-methylpropionate) and 2,2'-azobis(N-butyl-2-methylpropionamide); and peroxide polymerization initiators such as benzoyl peroxide, tert-butyl hydroperoxide, di-tert-butyl peroxide, tert-butyl perbenzoate, diisopropylbenzene peroxide, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, and 1,1-bis(tert-butylperoxy)cyclododecane.
[0164] Among these free radical polymerization initiators, azo polymerization initiators are preferred in terms of 10-hour half-life temperature and solubility in organic solvents, and more preferably at least one selected from 2,2'-azobis(isobutyronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile) and 2,2'-azobis(N-butyl-2-methylpropionamide).
[0165] The radical polymerization initiator may be used alone or in combination of two or more.
[0166] When step (i-2) is performed before step (i-1), the free radical polymerization initiator prepared in step (i-2) may be continuously used, or a free radical polymerization initiator may be further added in step (i-1) to replenish the free radical polymerization initiator deactivated in step (i-2). From the perspective of reactivity and molecular weight control, it is preferred to further add a free radical polymerization initiator in step (i-1).
[0167] The amount of the radical polymerization initiator added in step (i-1) is preferably 0.0001 to 1.0 parts by mass, more preferably 0.001 to 0.5 parts by mass, and further preferably 0.005 to 0.1 parts by mass, relative to the total amount of 100 parts by mass of the raw monomer group (mX), the raw monomer group (mY), and the optionally used ethylenically unsaturated compound having a functional group such as an isocyanate group. If it is 0.0001 parts by mass or more, polymerization can be carried out with an effective reaction time. If it is 1.0 parts by mass or less, a sufficiently high molecular weight block can be obtained.
[0168] From the viewpoint of allowing living radical polymerization to proceed preferentially over radical polymerization, the molar ratio of the radical generated from the radical polymerization initiator added in step (i-1) to the RAFT agent is preferably 1.0:1.0 to 1.0:1.5.
[0169] (Solvent)
[0170] As the solvent that can be used in step (i-1), a conventional solvent can be used. Examples of the solvent include esters such as ethyl acetate, propyl acetate, and butyl acetate; aromatic hydrocarbons such as toluene, xylene, and benzene; aliphatic hydrocarbons such as hexane and heptane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; ketones such as methyl ethyl ketone and methyl isobutyl ketone; glycols such as ethylene glycol, propylene glycol, and dipropylene glycol; glycol ethers such as methyl cellosolve, propylene glycol monomethyl ether, and dipropylene glycol monomethyl ether; glycol esters such as ethylene glycol diacetate and propylene glycol monomethyl ether acetate, etc. The solvent can be used alone or in combination of two or more.
[0171] When step (i-2) is performed before step (i-1), the solvent blended in step (i-2) may be used continuously or may be added in one step in step (i-1).
[0172] <Step (i-2)>
[0173] Step (i-2) is to prepare a catalyst having an SP value of 20 (J / cm 3 ) 1 / 2 A step of RAFT polymerization of the following raw material monomer group (mY) of the ethylenically unsaturated compound (m-3) and optionally a monomer other than (m-3).
[0174] The conditions such as reaction temperature, reaction time, polymerization method, concentration, etc. can be appropriately set in the same manner as in step (i-1).
[0175] For the RAFT agent, the same substance as that in step (i-1) can be used, and the preferred RAFT agent is also the same. When step (i-1) is performed before step (i-2), by continuing to use the RAFT agent formulated in step (i-1), a diblock copolymer can be obtained in which a block synthesized from the raw material monomer group (mY) is connected to a block synthesized from the raw material monomer group (mX).
[0176] For the free radical polymerization initiator, the same substance as that in step (i-1) can be used, and the preferred free radical polymerization initiator is also the same. When step (i-1) is performed before step (i-2), the free radical polymerization initiator prepared in step (i-1) can continue to be used, and in order to replenish the free radical polymerization initiator deactivated in step (i-1), a free radical polymerization initiator can be further added in step (i-2). From the aspects of reactivity and molecular weight control, it is preferred to further add a free radical polymerization initiator in step (i-2).
[0177] The amount of the radical polymerization initiator added in step (i-2) is preferably 0.0001 to 1.0 parts by mass, more preferably 0.001 to 0.5 parts by mass, and further preferably 0.005 to 0.1 parts by mass, relative to the total amount of 100 parts by mass of the raw monomer group (mX), the raw monomer group (mY), and the optionally used ethylenically unsaturated compounds having functional groups such as isocyanate groups. If it is 0.0001 parts by mass or more, polymerization can be carried out with an effective reaction time. If it is 1.0 parts by mass or less, a fully high molecular weight block can be obtained.
[0178] From the viewpoint of allowing living radical polymerization to proceed preferentially over radical polymerization, the molar ratio of the radical generated from the radical polymerization initiator added in step (i-2) to the RAFT agent is preferably 1.0:1.0 to 1.0:1.5.
[0179] The same solvent as that used in step (i-1) can be used as the solvent. When step (i-1) is performed before step (i-2), the solvent mixed in step (i-1) may be used continuously or may be further added in step (i-2).
[0180] <Step (ii)>
[0181] Process (ii) is a process for introducing ethylenically unsaturated groups by adding ethylenically unsaturated compounds to a part of the side chain hydroxyl groups of the copolymer obtained by process (i-1) and process (i-2). If ethylenically unsaturated compounds are added to all the side chain hydroxyl groups of the copolymer obtained by process (i-1) and process (i-2), hydroxyl groups are not included in the obtained copolymer, and the adhesive force as an adhesive sheet becomes insufficient. In addition, if ethylenically unsaturated compounds are added to all the side chain hydroxyl groups of the copolymer obtained by process (i-1) and process (i-2), the reaction site with the crosslinking agent (C) described later disappears. Therefore, addition is performed only on a part of the side chain hydroxyl groups. Specifically, when the side chain hydroxyl group is set to 100 mol%, the addition reaction is preferably 40 to 99 mol%. As a method for adding ethylenically unsaturated compounds, there is no particular limitation, and methods known in the technical field of this specification can be used. For (meth) acrylic resin (A), since the side chain has an ethylenically unsaturated group, the molecular chain length between the crosslinking points is relatively short compared to the (meth) acrylic copolymer into which an ethylenically unsaturated group is introduced at the end, and the crosslinking density can be effectively increased by UV irradiation. Therefore, in the case where (meth) acrylic resin (A) is used for a material of an adhesive, the adhesive force after UV irradiation can be greatly reduced. Therefore, the adhesive sheet using (meth) acrylic resin (A) is excellent in peelability from the adherend. In addition, the adhesive composition manufactured using (meth) acrylic resin (A) has excellent adhesion to the adhesive layer. Therefore, the adhesive composition manufactured using (meth) acrylic resin (A) is suitable for the adhesive layer of a cutting tape.
[0182] (catalyst)
[0183] In the addition reaction in step (ii), a known catalyst may be used as required. As a catalyst for adding the ethylenically unsaturated compound (a) containing an isocyanate group to the side chain hydroxyl group, for example, a urethanization catalyst such as dibutyltin dilaurate, diisopropoxybis(ethyl acetoacetate)titanium, tetrakis(2,4-pentanedione)zirconium, tris(2-ethylhexanoate)bismuth may be used.
[0184] When a catalyst is used when adding the isocyanate group-containing ethylenically unsaturated compound (a) to the side chain hydroxyl group in step (ii), the amount of the catalyst used is preferably 0.01 to 10 parts by mass, more preferably 0.02 to 5 parts by mass, and still more preferably 0.03 to 1 part by mass, relative to 100 parts by mass of the total of the copolymer obtained by steps (i-1) and (i-2) and the isocyanate group-containing ethylenically unsaturated compound (a).
[0185] (Inhibitor)
[0186] In the addition reaction in step (ii), a known polymerization inhibitor can be used as needed. As the polymerization inhibitor, a known polymerization inhibitor can be used, without particular limitation, and examples thereof include 4-methoxyphenol, hydroquinone, p-hydroxyanisole, 2,6-di-tert-butylphenol, 2,2'-methylenebis(4-methyl-6-tert-butylphenol) and phenothiazine. The polymerization inhibitor can be used alone or in combination of two or more.
[0187] When a polymerization inhibitor is used in step (ii), the amount of the polymerization inhibitor used is preferably 0.005 to 5 parts by mass, more preferably 0.03 to 3 parts by mass, and further preferably 0.05 to 1.5 parts by mass, relative to 100 parts by mass of the total of the copolymer and the ethylenically unsaturated compound obtained by steps (i-1) and (i-2). If the amount of the polymerization inhibitor used is 0.005 parts by mass or more, gelation during the addition reaction can be prevented. On the other hand, if the amount of the polymerization inhibitor used is 5 parts by mass or less, sufficient exposure sensitivity of the (meth) acrylic resin (A) can be obtained during UV irradiation.
[0188] (Reaction Conditions)
[0189] The temperature of the addition reaction is preferably 25° C. to 130° C., particularly preferably 40° C. to 90° C. If the temperature of the addition reaction is 25° C. or higher, a sufficient reaction rate can be obtained. If the temperature of the addition reaction is 130° C. or lower, crosslinking of the double bond portion due to free radical polymerization by heat and generation of a gel can be prevented.
[0190] During the addition reaction, a gas having a polymerization inhibitory effect may be introduced into the reaction system. By introducing a gas having a polymerization inhibitory effect into the reaction system, gelation during the addition reaction can be prevented.
[0191] Examples of the gas having the polymerization inhibition effect include a gas containing oxygen to a degree that does not enter the explosion range of the substances in the system, such as air.
[0192] It is more preferable to use a gas having a polymerization inhibitor effect together with a polymerization inhibitor, because this can reduce the amount of the polymerization inhibitor used or improve the polymerization inhibitor effect.
[0193] [Method for producing adhesive composition]
[0194] <Process (iii)>
[0195] The pressure-sensitive adhesive composition can be produced, for example, by a method including the step (iii) of mixing the (meth)acrylic resin (A), the photopolymerization initiator (B), the crosslinking agent (C), and other components as needed.
[0196] The method for mixing the components contained in the adhesive composition is not particularly limited, and the mixing can be performed using, for example, a homodispersor or a stirring device equipped with a stirring blade such as a paddle blade.
[0197] [Method for producing photo-crosslinkable adhesive]
[0198] Step (iv)
[0199] The photo-crosslinkable adhesive can be produced, for example, by a method comprising the step (iv) of applying the adhesive composition onto a substrate or a release sheet and thermally curing the composition.
[0200] The PSA composition obtained in step (iii) may be used as it is, or a PSA composition having a viscosity adjusted by further adding a solvent may be used.
[0201] Thermal curing is performed by heating, drying and aging as needed during the formation of the photo-crosslinkable adhesive. For example, as one embodiment of step (iv), an adhesive composition is applied to a substrate, and heated and dried to remove the solvent when a solvent is contained, thereby forming an adhesive composition layer. Then, a release sheet is attached to the adhesive composition layer as needed. Moreover, the obtained sheet is aged in an oven for a certain period of time as needed to form a crosslinked structure, thereby obtaining a layer of a photo-crosslinkable adhesive.
[0202] According to another embodiment, step (iv) includes a step (iv-1) of applying the adhesive composition to a release sheet to obtain an adhesive composition layer, a step (iv-2) of thermally curing the adhesive composition layer to obtain a photo-crosslinkable adhesive layer, and a step (iv-3) of laminating a substrate on the adhesive composition layer or the photo-crosslinkable adhesive layer. Step (iv-3) can be performed between step (iv-1) and step (iv-2), or after step (iv-2). For example, an adhesive composition is applied to a release sheet, and the solvent is removed by heating and drying in the presence of a solvent to form an adhesive composition layer (step (iv-1)). Then, a release sheet having an adhesive composition layer is arranged on a substrate in a manner such that the surface of the adhesive composition layer side faces the substrate, and the adhesive composition layer is transferred to the substrate (step (iv-3)). Furthermore, the obtained sheet is aged in an oven for a certain period of time as needed to form a crosslinked structure, thereby obtaining a photo-crosslinkable adhesive layer (step (iv-2)).
[0203] As the method for applying the adhesive composition to the substrate or the release sheet, a known method can be used. Specifically, a method for applying using a conventional coating machine, such as a gravure roll coater, a reverse roll coater, a lick coater, a dip roll coater, a rod coater, a knife coater, a spray coater, a comma coater, a direct coater, etc. can be cited.
[0204] There is no particular restriction on the conditions for heating and drying the applied adhesive composition, and the heating and drying is usually carried out at 25 to 180°C, preferably at 60 to 150°C, for 1 to 20 minutes, preferably 1 to 10 minutes. By heating and drying within the above range, the solvent contained in the adhesive composition can be removed. There is no particular restriction on the conditions for aging the heat-dried sheet in an oven for a certain period of time, and the aging is usually carried out at 25 to 100°C, preferably at 30 to 80°C, for 1 to 30 days, preferably 1 to 14 days. By aging under the above conditions, the (meth) acrylic resin (A) can be cross-linked using a crosslinking agent (C), and the gel fraction of the photo-crosslinkable adhesive can be adjusted to the desired range.
[0205] [Adhesive sheet]
[0206] The adhesive sheet has a substrate layer and an adhesive layer formed by a thermosetting material or a photothermosetting material of the adhesive composition. For the adhesive sheet, a release sheet can be provided on the exposed surface of the adhesive layer (i.e., the surface on the opposite side of the substrate layer) as needed before pasting the adherend. For the adhesive sheet, for example, it can be obtained by step (iv). In the state of being pasted on the adherend, the adhesive layer is used in the state of a photocrosslinkable adhesive layer, and when peeled off from the adherend, it is peeled off in the state of crosslinking the photocrosslinkable adhesive layer by UV irradiation so as to reduce the adhesive force.
[0207] The substrate is not particularly limited and can be appropriately selected according to the purpose. Resin films are usually preferred. As resin materials, for example, polyvinyl chloride, polyvinylidene chloride, polyolefin (PO), polyester, polyurethane, polycarbonate, polyetheretherketone, polyimide, polyetherimide, polyamide, fully aromatic polyamide (aromatic polyamide), polyphenylene sulfide, fluororesin, cellulose resin and silicone resin can be listed. As polyolefins, for example, polyethylene (PE) such as low-density polyethylene, linear polyethylene, medium-density polyethylene, high-density polyethylene, ultra-low-density polyethylene, etc. can be listed; polypropylene (PP) such as random copolymer polypropylene, block copolymer polypropylene, homopolypropylene, etc.; polybutene; polymethylpentene; ethylene-vinyl acetate copolymer; ionomer resin; ethylene-(meth) acrylic acid copolymer; ethylene-(meth) acrylic acid ester copolymer; ethylene-butene copolymer; and ethylene-hexene copolymer. As polyesters, for example, polyethylene terephthalate (PET), polyethylene naphthalate and polybutylene terephthalate (PBT) can be listed. Among these resin materials, in order to obtain an adhesive sheet with moderate flexibility, it is particularly preferred to use one or more selected from PE, PP and PET. The resin material used as the substrate material can be used only one, or two or more can be mixed and used. In the case of being used for cutting tape, polyolefin is preferably used.
[0208] The substrate may be composed of one material or two or more materials. The substrate may have a single layer structure or a multilayer structure. Since the photo-crosslinkable adhesive on the substrate is a UV-curable type, the substrate preferably has UV transmittance. When the substrate is a resin film, the substrate may be a non-stretched film, a uniaxially stretched film, or a biaxially stretched film.
[0209] The substrate may be a substrate that has been subjected to a treatment for improving adhesion. Such treatments include physical treatments such as corona discharge treatment, plasma treatment, sand pad processing, ozone exposure treatment, flame exposure treatment, high voltage electric shock exposure treatment, ionizing radiation treatment, chemical treatments such as chromic acid treatment, and primer treatment.
[0210] As the substrate, a PO film is preferably used. The heat resistance of the PO film is low and is not suitable for the above-mentioned heating and drying temperature. Therefore, it is preferred to apply the adhesive composition on the release sheet, heat and dry to remove the solvent, and then transfer the adhesive composition layer to adhere to the PO film. Specifically, it is preferred to apply the adhesive composition on the surface of the silicone-based lightly peeled PET film to which a demoulding treatment has been implemented, heat and dry, and in a manner that the corona-treated surface of the PO film is bonded to the exposed surface of the adhesive composition layer, use a rubber roller to paste the PO film on the adhesive composition layer.
[0211] The release sheet is not particularly limited, and for example, a release sheet commonly used in adhesive applications can be used without limitation. Specifically, a resin film identical to the resin film used in the above-mentioned substrate is preferred, and from the perspective of handling, a resin film comprising one or more selected from PE, PP and PET is preferably used.
[0212] In order to impart easy release properties, the release sheet may be subjected to a release treatment, and specifically, a release treatment using silicone may be used.
[0213] The thickness of the photo-crosslinkable adhesive layer is preferably 5 to 100 μm, more preferably 10 to 50 μm, and even more preferably 10 to 20 μm. When the thickness of the photo-crosslinkable adhesive layer is 5 μm or more, sufficient adhesive properties are exhibited and coating is also easy. When the thickness of the photo-crosslinkable adhesive layer is 100 μm or less, the generation of bubbles and the residual solvent during heat drying can be suppressed.
[0214] [Application of adhesive sheet]
[0215] Adhesive sheet can be used as a re-peelable adhesive sheet when, for example, manufacturing electronic components. Specifically, the re-peelable adhesive sheet can be used as a surface protection tape for protecting the surface of the adherend in each process when manufacturing electronic components. Adhesive sheet can also be used for the following purposes, that is, in each process when manufacturing electronic components, the adherend is fixed, and after various processing steps are implemented, UV (ultraviolet rays) are irradiated and peeled off from the adherend. Therefore, adhesive sheet can be used as back grinding tape, dicing tape, dicing / chip bonding integrated film, etc. when processing semiconductor wafers. Adhesive sheet can also be used as support tape for fragile components such as extremely thin glass substrates and components that are easily warped such as FPC substrates, etc. In particular, adhesive sheet has excellent water resistance and sufficient adhesion to the adherend, and is therefore suitable for dicing tape and dicing / chip bonding integrated film.
[0216] [Cutting tape]
[0217] The dicing tape includes a base material layer and an adhesive layer formed of a thermally cured product or a photothermocured product of an adhesive composition.
[0218] Hereinafter, an exemplary method of using the adhesive sheet as a dicing tape for a wafer is described. Before the dicing process is performed, the adhesive sheet is pasted on a wafer formed with a plurality of components. Next, the wafer is cut and divided (cut) into individual components to form component pieces (chips). Then, the adhesive sheet pasted on each component piece is irradiated with UV. Thus, the photo-crosslinkable adhesive layer is irradiated with UV through the substrate of the adhesive sheet, and the unsaturated bonds in the photo-crosslinkable adhesive form a three-dimensional crosslinked structure and solidify. As a result, the adhesive force of the adhesive layer is reduced. Then, the adhesive sheet is peeled off from each component piece.
[0219] [Method for manufacturing dicing tape]
[0220] The dicing tape can be produced, for example, by forming a photo-crosslinkable adhesive layer on a substrate. The photo-crosslinkable adhesive layer can be formed, for example, by the same method as in the above step (iv).
[0221] The substrate is preferably a substrate made of a material suitable for the expansion step, and is preferably a polyolefin film.
[0222] When a polyolefin film is used, heating during the formation of the photo-crosslinkable adhesive layer may sometimes be a problem from the perspective of heat resistance.
[0223] The steps of applying the adhesive composition on a release sheet to obtain an adhesive composition layer (iv-1), thermally curing the adhesive composition layer to obtain a photo-crosslinkable adhesive layer (iv-2), and
[0224] a step (iv-3) of laminating a substrate on the photo-crosslinkable adhesive layer,
[0225] The obtained sheet is aged in an oven for a certain period of time as required to form a cross-linked structure.
[0226] The thickness of the photo-crosslinkable adhesive layer is preferably 5 to 100 μm, more preferably 10 to 50 μm, and further preferably 10 to 20 μm. When the thickness of the photo-crosslinkable adhesive layer is 5 μm or more, sufficient adhesive properties are exhibited and coating is also easy. When the thickness of the photo-crosslinkable adhesive layer is 100 μm or less, the generation of bubbles and the residual solvent during heat drying can be suppressed. In particular, if the thickness of the photo-crosslinkable adhesive layer is 10 to 20 μm, sufficient peelability and splitting (cutting) properties can be obtained.
[0227] [Dicing / die bonding integrated film]
[0228] The dicing die-bonding integrated film includes a base material layer, an adhesive layer formed of a thermally cured product or a photothermocured product of an adhesive composition, and an adhesive layer in this order.
[0229] [Method for manufacturing dicing / die bonding integrated film]
[0230] The dicing / die-bonding integrated film can be obtained, for example, by laminating a dicing tape and a die-bonding tape. The dicing tape can be produced, for example, by the same method as the above-mentioned production method.
[0231] The method for producing the dicing die-bonding integrated film may include, for example, a method including the following steps.
[0232] A step (iv-1) of applying the adhesive composition on a release sheet to obtain an adhesive composition layer;
[0233] Step (iv-2) of thermally curing the adhesive composition layer to obtain a photo-crosslinkable adhesive layer,
[0234] A step (iv-3) of laminating a substrate on the adhesive composition layer or the photo-crosslinkable adhesive layer to obtain a dicing tape, and a step (v) of laminating the dicing tape and the die bonding tape.
[0235] The order of the steps may be reversed except that step (iv-1) is performed first and step (v) is performed last. Step (iv-3) may be performed between step (iv-1) and step (iv-2) or after step (iv-2).
[0236] The thickness of the photo-crosslinkable adhesive layer is preferably 5 to 100 μm, more preferably 10 to 50 μm, and further preferably 10 to 20 μm. When the thickness of the photo-crosslinkable adhesive layer is 5 μm or more, sufficient adhesive properties are exhibited and coating is also easy. When the thickness of the photo-crosslinkable adhesive layer is 100 μm or less, the generation of bubbles and the residual solvent during heat drying can be suppressed. In particular, if the thickness of the photo-crosslinkable adhesive layer is 10 to 20 μm, sufficient peelability and splitting (cutting) properties can be obtained.
[0237] Step (v) can be performed, for example, by preparing a die bonding tape and pressing it with a dicing tape. The die bonding tape can be obtained, for example, by coating an adhesive composition on a release sheet and curing it to form an adhesive layer. The bonding temperature is, for example, 30 to 50° C. The bonding pressure (linear pressure) is, for example, 0.1 to 20 kgf / cm.
[0238] As a modified example of the method for manufacturing a dicing / die bonding integrated film, the thermal curing of the adhesive composition may be performed in two steps, step (iv-2) and step (v). For example, after thermal curing in step (iv-2), the dicing tape and the die bonding tape may be laminated in step (v), and then cured to further thermally cure the photo-crosslinkable adhesive layer.
[0239] As a modified example of the method for manufacturing a dicing / chip bonding integrated film, the release sheet in step (iv-1) can be replaced with the chip bonding tape in step (v), and the formation of the photo-crosslinkable adhesive layer and the lamination of the dicing tape and the chip bonding tape can be performed at one time. In this case, the adhesive composition is applied to the adhesive layer of the chip bonding tape, which is thermally cured, and the substrate is laminated before or after the thermal curing, thereby obtaining a dicing / chip bonding integrated film.
[0240] [Method for producing cured product (photothermal cured product) of photo-crosslinkable adhesive]
[0241] Step (vi)
[0242] The cured product of the photo-crosslinkable adhesive (also referred to as a photothermal cured product) can be produced, for example, by a method including the step (vi) of irradiating the photo-crosslinkable adhesive with UV light to form a crosslinked structure.
[0243] Examples of the light source used for UV irradiation include a high-pressure mercury lamp, an ultrahigh-pressure mercury lamp, a carbon arc lamp, a xenon lamp, a metal halide lamp, a chemical lamp, and a black light.
[0244] The UV irradiation dose for irradiating the photo-crosslinkable adhesive is preferably 50 to 3,000 mJ / cm 2 , more preferably 100 to 600 mJ / cm 2 . If the UV irradiation dose to the photo-crosslinkable adhesive is 50 mJ / cm2 or more, the crosslinking density of the photo-crosslinkable adhesive can be increased at a sufficiently fast curing speed by UV irradiation. Therefore, when the photo-crosslinkable adhesive is used for the adhesive layer, the adhesive force of the adhesive layer after UV irradiation can be sufficiently reduced. When the photo-crosslinkable adhesive is used for the resist, the strength can be improved. Even if the UV irradiation dose to the photo-crosslinkable adhesive exceeds 3,000 mJ / cm 2 , the crosslink density could not be further increased. Therefore, the UV irradiation dose was increased to 3,000 mJ / cm 2 In this way, the influence of UV irradiation on the adherend can be reduced, and a cured product can be produced economically. Therefore, when a photo-crosslinkable adhesive is used for a pressure-sensitive adhesive sheet, peeling can be performed economically.
[0245] Example
[0246] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0247] The raw materials used in the synthesis of (meth)acrylic resins (A) and (cA) are listed below. It should be noted that in Table 1, the SP value ((J / cm 3 ) 1 / 2 ).
[0248] Raw material monomer:
[0249] 2-Hydroxyethyl acrylate, Osaka Organic Chemical Industry Co., Ltd.
[0250] Styrene, Asahi Kasei Co., Ltd.
[0251] Isostearyl acrylate, Osaka Organic Chemical Industry Co., Ltd.
[0252] n-Butyl acrylate, Osaka Organic Chemical Industry Co., Ltd.
[0253] Cyclohexyl acrylate, Osaka Organic Chemical Industry Co., Ltd.
[0254] Methyl acrylate, Nippon Shokubai Co., Ltd.
[0255] Methyl methacrylate, Nippon Shokubai Co., Ltd.
[0256] Isopropylene methacrylate, Kurara Co., Ltd.
[0257] Free Radical Polymerization Initiator:
[0258] 2,2'-Azobis(N-butyl-2-methylpropionamide), Fujifilm Wako Pure Chemical Industries, Ltd.
[0259] 2,2'-Azobis(isobutyronitrile), Fujifilm Wako Pure Chemical Industries, Ltd.
[0260] 2,2'-Azobis(2,4-dimethylvaleronitrile), Fujifilm Wako Pure Chemical Industries, Ltd.
[0261] RAFT agent:
[0262] Benzyldodecyl trithiocarbonate, Fujifilm Wako Pure Chemical Industries, Ltd.
[0263] 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]valeric acid, Fujifilm Wako Pure Chemical Industries, Ltd.
[0264] Bis[[4-[[ethyl-(2-acetoxyethyl)amino]carbonyl]phenyl]methyl]trithiocarbonate, Fujifilm Wako Pure Chemical Industries, Ltd.
[0265] 2-cyano-2-propyldodecyltrithiocarbonate, Fujifilm Wako Pure Chemical Industries, Ltd.
[0266] Ethylenically unsaturated compound containing an isocyanate group (a):
[0267] Karenz (Karenz) (trademark) MOI, 2-isocyanatoethyl methacrylate, RESONAC CO., LTD. Aoi-VM (trademark), 2-isocyanatoethyl acrylate, RESONAC CO., LTD.
[0268] The following is a synthesis example of (meth)acrylic resins (A) and (cA). The weight average molecular weight (Mw), molecular weight distribution (Mw / Mn) and hydroxyl value of (meth)acrylic resins (A) and (cA) were measured and calculated by the above-mentioned method. The ethylenically unsaturated group equivalent of (meth)acrylic resins (A) and (cA) was calculated from the feed amount as described above.
[0269] [Synthesis example 1]
[0270] (Process i-2)
[0271] In a reaction apparatus equipped with a stirrer, a temperature controller, a reflux condenser, a dropping funnel and a thermometer, 25 mol of styrene, 0.118 parts by mass of benzyl dodecyl trithiocarbonate based on 100 parts by mass of the total of the raw material monomer group (mX) and (mY) and the isocyanate group-containing ethylenically unsaturated compound (a), 0.0417 parts by mass of 2,2'-azobis(N-butyl-2-methylpropionamide) based on 100 parts by mass of the total of the raw material monomer group (mX) and (mY) and the isocyanate group-containing ethylenically unsaturated compound (a), and butyl acetate as a solvent were added so that the total concentration of the raw material monomer group (mY), the RAFT agent and the radical polymerization initiator became 80% by mass. The temperature was raised to 120° C., and the mixture was reacted for 14 hours.
[0272] (Process i-1)
[0273] Next, 58 mol of n-butyl acrylate, 17 mol of 2-hydroxyethyl acrylate, 0.0417 parts by mass of 2,2'-azobis(N-butyl-2-methylpropionamide) relative to 100 parts by mass of the raw monomer group (mX) and (mY) and the isocyanate group-containing ethylenically unsaturated compound (a), and butyl acetate as a solvent were added so that the total concentration of the polymer obtained in step (i-2), the raw monomer group (mX) and the radical polymerization initiator added in step (i-1) became 80% by mass. The mixture was heated to 120° C. and reacted for 14 hours.
[0274] (Process ii)
[0275] Next, the reactant is cooled to room temperature and diluted with butyl acetate so that the concentration of the copolymer obtained in step (i-1) becomes 40% by mass. Next, the temperature of the diluted reactant is raised to 55°C, and a mixed solution of 16 mol of 2-isocyanatoethyl acrylate and dibutyltin dilaurate as a urethanization catalyst is added dropwise through a dropping funnel. The amount of dibutyltin dilaurate is 0.06 parts by mass relative to a total of 100 parts by mass of the copolymer obtained in step (i-1) and the isocyanate-containing ethylenically unsaturated compound (a). After the addition is completed, the reaction system is maintained at 60°C for 4 hours to eliminate the isocyanate group. Thus, a liquid containing a (meth) acrylic resin (A1) having a weight average molecular weight of 300,000, a molecular weight distribution of 2.6, an ethylenically unsaturated group equivalent of 905 g / mol, and a hydroxyl value of 5.05 mgKOH / g and a solid content of 40% by mass is obtained.
[0276] [Synthesis Examples 2 to 7]
[0277] (Meth)acrylic resins [A2] to [A7] were obtained by the same operation as in Synthesis Example 1 except that the composition shown in Table 1 was used. In Synthesis Example 3, step (ii) was not performed.
[0278] [Comparative Synthesis Example 1]
[0279] (Process i-1)
[0280] In a reaction apparatus equipped with a stirrer, a temperature controller, a reflux condenser, a dropping funnel and a thermometer, 6 mol of n-butyl acrylate, 16 mol of 2-hydroxyethyl acrylate, 0.260 parts by mass of bis[[4-[[ethyl-(2-acetoxyethyl)amino]carbonyl]phenyl]methyl]trithiocarbonate based on 100 parts by mass of the total of the raw material monomer group (mX) and (mY) and the isocyanate group-containing ethylenically unsaturated compound (a), 0.0160 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile) based on 100 parts by mass of the total of the raw material monomer group (mX) and (mY) and the isocyanate group-containing ethylenically unsaturated compound (a), and ethyl acetate as a solvent were added so that the total concentration of the raw material monomer group (mX), the RAFT agent and the radical polymerization initiator became 50% by mass. The temperature was raised to 60° C. and the reaction was carried out for 7 hours.
[0281] (Process i-2)
[0282] Next, 78 mol of n-butyl acrylate, 0.0160 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile) based on 100 parts by mass of the total of the raw material monomer group (mX) and (mY) and the isocyanate group-containing ethylenically unsaturated compound (a), and ethyl acetate as a solvent were added so that the total concentration of the copolymer obtained in step (i-1), the raw material monomer group (mY) and the radical polymerization initiator added in step (i-2) became 50% by mass. The temperature was raised to 60° C. and the mixture was reacted for 14 hours.
[0283] (Process ii)
[0284] Next, the reactant is cooled to room temperature and diluted with ethyl acetate so that the concentration of the copolymer obtained in step (i-2) becomes 40% by mass. Next, the temperature of the diluted reactant is raised to 55°C, and a mixed solution of 13 mol of 2-isocyanatoethyl methacrylate and dibutyltin dilaurate as a urethanization catalyst is added dropwise through a dropping funnel. The amount of dibutyltin dilaurate is 0.06 parts by mass relative to a total of 100 parts by mass of the copolymer obtained in step (i-2) and the ethylenically unsaturated compound (a) containing an isocyanate group. After the addition is completed, the reaction system is maintained at 60°C for 4 hours to eliminate the isocyanate group. Thus, a liquid containing an XYX-type (meth) acrylic resin (cA1) having a weight average molecular weight of 300,000, a molecular weight distribution of 2.4, an ethylenically unsaturated group equivalent of 1109 g / mol, and a hydroxyl value of 11.46 mgKOH / g and a solid content of 40% by mass is obtained.
[0285] [Comparative Synthesis Example 2]
[0286] Except having used the composition shown in Table 1, the same operation as in Comparative Synthesis Example 1 was carried out to obtain an XYX-type (meth)acrylic resin (cA2).
[0287] [Comparative Synthesis Example 3]
[0288] (Process i-1)
[0289] In a reaction apparatus equipped with a stirrer, a temperature controller, a reflux condenser, a dropping funnel and a thermometer, 18 mol of styrene, 10 mol of 2-hydroxyethyl acrylate, 0.156 parts by mass of 4-cyano-4-[(dodecylsulfanylthiocarbonyl)sulfanyl]pentanoic acid based on 100 parts by mass of the total of the raw material monomer group (mX) and (mY) and the isocyanate group-containing ethylenically unsaturated compound (a), 0.0405 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile) based on 100 parts by mass of the total of the raw material monomer group (mX) and (mY) and the isocyanate group-containing ethylenically unsaturated compound (a), and butyl acetate as a solvent were added so that the total concentration of the raw material monomer group (mX), the RAFT agent and the radical polymerization initiator became 80% by mass. The temperature was raised to 120° C. and the reaction was carried out for 14 hours.
[0290] (Process i-2)
[0291] Next, 62 mol of n-butyl acrylate, 10 mol of 2-hydroxyethyl acrylate, 0.0405 parts by mass of 2,2'-azobis(2,4-dimethylvaleronitrile) based on 100 parts by mass of the total of the raw material monomer group (mX) and (mY) and the isocyanate group-containing ethylenically unsaturated compound (a), and butyl acetate as a solvent were added so that the total concentration of the copolymer obtained in step (i-1), the raw material monomer group (mY) and the radical polymerization initiator added in step (i-2) became 80% by mass. The mixture was heated to 120° C. and reacted for 14 hours.
[0292] (Process ii)
[0293] Next, the reactant is cooled to room temperature and diluted with butyl acetate so that the concentration of the copolymer obtained in step (i-2) becomes 40% by mass. Next, the temperature of the diluted reactant is raised to 55°C, and a mixed solution of 18 mol of 2-isocyanatoethyl acrylate and dibutyltin dilaurate as a urethanization catalyst is added dropwise through a dropping funnel. The amount of dibutyltin dilaurate is 0.06 parts by mass relative to a total of 100 parts by mass of the copolymer obtained in step (i-2) and the ethylenically unsaturated compound (a) containing an isocyanate group. After the addition is completed, the reaction system is maintained at 60°C for 4 hours to eliminate the isocyanate group. Thus, a liquid containing a (meth) acrylic resin (cA3) having a weight average molecular weight of 250,000, a molecular weight distribution of 2.4, an ethylenically unsaturated group equivalent of 833g / mol, and a hydroxyl value of 9.41mgKOH / g and a solid content of 40% by mass is obtained.
[0294] [Comparative Synthesis Example 4]
[0295] (Process i-1)
[0296] In a reaction container, 63 mol of n-butyl acrylate, 17 mol of 2-hydroxyethyl acrylate, 20 mol of isostearyl acrylate, 0.135 parts by mass of benzyl dodecyl trithiocarbonate based on 100 parts by mass of the total of the raw material monomer group (mX) and the isocyanate group-containing ethylenically unsaturated compound (a), 0.0563 parts by mass of 2,2'-azobis(isobutyronitrile) based on 100 parts by mass of the total of the raw material monomer group (mX) and the isocyanate group-containing ethylenically unsaturated compound (a), and butyl acetate as a solvent were added so that the total concentration of the raw material monomer group (mX), the RAFT agent, and the radical polymerization initiator became 80% by mass. The temperature was raised to 120° C., and the mixture was reacted for 14 hours.
[0297] (Process ii)
[0298] Next, the reactant is cooled to room temperature and diluted with butyl acetate so that the concentration of the copolymer obtained in step (i-1) becomes 40% by mass. Next, the temperature of the diluted reactant is raised to 55°C, and a mixed solution of 15 mol of 2-isocyanatoethyl acrylate and dibutyltin dilaurate as a urethanization catalyst is added dropwise through a dropping funnel. The amount of dibutyltin dilaurate is 0.06 parts by mass relative to a total of 100 parts by mass of the copolymer obtained in step (i-1) and the isocyanate-containing ethylenically unsaturated compound (a). After the addition is completed, the reaction system is maintained at 60°C for 4 hours to eliminate the isocyanate group. Thus, a liquid containing a (meth) acrylic resin (cA4) having a weight average molecular weight of 280,000, a molecular weight distribution of 2.1, an ethylenically unsaturated group equivalent of 1221 g / mol, and a hydroxyl value of 5.04 mgKOH / g and a solid content of 40% by mass is obtained.
[0299] [Comparative Synthesis Example 5]
[0300] (Process i-1)
[0301] Butyl acetate as a solvent was added to the reaction vessel so that the total concentration of the raw material monomer group (mX) and the free radical polymerization initiator became 60% by mass. 63 mol of n-butyl acrylate, 17 mol of 2-hydroxyethyl acrylate, 20 mol of isostearyl acrylate, and 0.297 mass parts of 2,2'-azobis(isobutyronitrile) relative to a total of 100 mass parts of the raw material monomer group (mX) and the ethylenically unsaturated compound (a) containing an isocyanate group were mixed to prepare a mixed solution. After the butyl acetate in the reaction vessel was heated to 80°C, the mixed solution was added dropwise over 3 hours. After the addition was completed, the reaction was continued at 80°C for 4 hours.
[0302] (Process ii)
[0303] Next, the reactant is cooled to room temperature and diluted with butyl acetate so that the concentration of the copolymer obtained in step (i-1) becomes 40% by mass. Next, the temperature of the diluted reactant is raised to 55°C, and a mixed solution of 15 mol of 2-isocyanatoethyl acrylate and dibutyltin dilaurate as a urethanization catalyst is added dropwise through a dropping funnel. The amount of dibutyltin dilaurate is 0.06 parts by mass relative to a total of 100 parts by mass of the copolymer obtained in step (i-1) and the isocyanate-containing ethylenically unsaturated compound (a). After the addition is completed, the reaction system is maintained at 60°C for 4 hours to eliminate the isocyanate group. Thus, a liquid containing a (meth) acrylic resin (cA5) having a weight average molecular weight of 320,000, a molecular weight distribution of 4.2, an ethylenically unsaturated group equivalent of 1221 g / mol, and a hydroxyl value of 5.04 mgKOH / g and a solid content of 40% by mass is obtained.
[0304]
[0305]
[0306]
[0307]
[0308] The raw materials used to prepare the adhesive composition are listed below.
[0309] Photopolymerization initiator (B):
[0310] TPO: 2,4,6-trimethylbenzoyldiphenylphosphine oxide (BASF, trade name: L-TPO)
[0311] Irgacure 500: A mixture of 1-hydroxycyclohexyl phenyl ketone and benzophenone (BASF, trade name: Irgacure 500)
[0312] Crosslinking agent (C)
[0313] TAKENET: Trimethylolpropane toluene diisocyanate adduct (Mitsui Chemicals, Inc., trade name: TAKENET D-101E)
[0314] L-55E: trimethylolpropane toluene diisocyanate adduct (Tosoh Corporation, trade name: Coronate L-55E)
[0315] L-45E: trimethylolpropane toluene diisocyanate adduct (Tosoh Corporation, trade name: Coronet L-45E)
[0316] [Preparation of Adhesive Composition]
[0317] Ethyl acetate was added as a diluent solvent to the liquid containing (meth)acrylic resins (A1) to (A7) and (cA1) to (cA5) obtained in Synthesis Examples 1 to 7 and Comparative Synthesis Examples 1 to 5, and the content of each of the (meth)acrylic resins (A1) to (A7) and (cA1) to (cA5) was adjusted to 30% by mass. Using this liquid, a pressure-sensitive adhesive composition was obtained by the method shown below.
[0318] In a room where active rays are blocked, the (meth)acrylic resin (A) or (cA), a photopolymerization initiator (B) and a crosslinking agent (C) shown in Table 2 are added to a plastic container in the amounts (parts by mass) shown in Table 2 and stirred to obtain adhesive compositions (B1) to (B7) and (cB1) to (cB5).
[0319] [Example 1] Preparation of adhesive sheet
[0320] As a release sheet, a silicone light release PET film (Toyobo Co., Ltd., trade name: E7006, thickness 25 μm) was prepared. For the surface subjected to demolding treatment, the adhesive composition (B1) was applied using an applicator in a manner that the thickness after thermal curing became 11 μm, and heated and dried at 110°C for 2 minutes to form an adhesive composition layer. Next, as a sheet-like substrate, a PO film with a thickness of 90 μm was prepared. The PO film was pasted on the adhesive composition layer using a rubber roller in a manner that the corona-treated surface of the PO film was bonded to the exposed surface of the adhesive composition layer. The adhesive composition layer was cross-linked and cured in an oven at 40°C for 3 days to obtain the adhesive sheet of Example 1.
[0321] [Examples 2 to 7 and Comparative Examples 1 to 5] Preparation of Adhesive Sheets
[0322] The same procedures as in Example 1 were performed except that adhesive compositions [B2] to [B7] and [cB1] to [cB5] were used instead of adhesive composition [B1], respectively, and the thickness of the adhesive composition layer after thermal curing was as shown in Table 2, to obtain adhesive sheets of Examples 2 to 7 and Comparative Examples 1 to 5.
[0323] [Adhesion Evaluation]
[0324] (1) Determination of initial adhesion (180° peel strength)
[0325] As described below, the adhesion of the adhesive sheets of the embodiments and comparative examples to the wafer was evaluated by measuring the 180° peel strength. Samples with a width of 25 mm and a length of 100 mm were cut from the adhesive sheets of Examples 1 to 7 and Comparative Examples 1 to 5. The silicone-based light peeling PET film was peeled off to expose the adhesive layer and bonded to a test dummy wafer (AS ONE Co., Ltd.) with a rubber roller. An autoclave (TAC-200, Sakura Seiki Co., Ltd.) was used for crimping to obtain a sample for adhesion measurement. Using a tensile testing machine (TAXT2i, Stable Micro Systems), the peel strength of the adhesive sheet to the wafer was measured and determined as the initial adhesion. The measurement conditions were set to a peel angle of 180° and a tensile speed of 5 mm / sec. It should be noted that the storage of the sample and the measurement of the peel strength were carried out at a temperature of 23°C and a relative humidity of 40%. The results are shown in Table 2.
[0326] (2) Determination of adhesion after immersion (180° peel strength)
[0327] The same method as (1) for measuring the initial adhesion (180° peel strength) is used to prepare a sample for measuring adhesion. The obtained sample is immersed in ion exchange water and allowed to stand in a dark place for 3 hours at a temperature of 23°C and a relative humidity of 40%. The sample after immersion treatment is taken out, and after removing excess water, the peel strength of the adhesive sheet to the wafer is measured using the same method as (1) for measuring the initial adhesion (180° peel strength), and is determined as the adhesion after immersion. Based on the measurement results, the adhesion change rate is calculated using the following formula. The results are shown in Table 2.
[0328] Adhesion change rate (%) = ((adhesion after immersion) - (initial adhesion) / (initial adhesion)) × 100
[0329] (3) Determination of adhesion (30° peel strength) after UV irradiation
[0330] A sample for measuring the adhesive strength was prepared by the same method as in (1) the measurement of the initial adhesive strength (180° peel strength). The substrate side of the adhesive sheet of the obtained sample was irradiated at a dose of 300 mJ / cm 2 The samples were irradiated with ultraviolet light (UV) under the conditions of , and the samples for measuring the adhesive strength after UV irradiation were obtained. The UV irradiation was performed using a conveyor-type ultraviolet irradiation device (Igrapix Co., Ltd., 2 kW lamp, 80 W / cm). Then, the peel strength of the adhesive sheet to the wafer was measured using the same method as (1) for measuring the initial adhesive strength (180° peel strength), except that the peeling angle was changed to 30°, and was determined as the adhesive strength after UV irradiation. The results are shown in Table 2.
[0331]
[0332]
[0333] [Production of dicing / die bonding integrated film]
[0334] The cover film on one side of the die bonding film (FH-D25T-50, Resonac Co., Ltd.) in which both sides of the adhesive layer are protected by cover films was peeled off to expose the adhesive layer. The adhesive layer was bonded to the adhesive layer of the adhesive sheets of Examples 1 to 7 and Comparative Examples 1 to 5 in which the light-peel PET film was peeled off to expose the adhesive layer using a rubber roller. The film was left at room temperature for 1 day to obtain a dicing / die bonding integrated film.
[0335] [Processability Evaluation]
[0336] (1) Blade cutting test (cutting performance)
[0337] Using the dicing / chip bonding integrated film, semiconductor wafers were diced according to the following procedures. The number of semiconductor chips that were scattered among the diced semiconductor chips (total number: 400) was counted, that is, the number of semiconductor chips that were separated from the dicing / chip bonding integrated film and scattered was calculated, and the chip scattering rate (%) was used as an evaluation of the dicing performance. Therefore, the closer the chip scattering rate is to 0%, the better the dicing performance is.
[0338] First, the semiconductor wafer (8 inches in diameter, 0.6 mm thick, silicon mirror wafer) was back-grinded to obtain a mirror wafer with a thickness of 0.2 mm. Next, the mirror wafer was roll-bonded and bonded at 70°C on the adhesive layer exposed by peeling off the cover film from the dicing / chip bonding integrated film. The mirror wafer was then cut. The mirror wafer was fully cut in a manner to form a chip size of 1.0 mm square. The bonding conditions and cutting conditions are as follows.
[0339] <Semiconductor Wafer Polishing Conditions>
[0340] Grinding device: Trade name DFG-8560 (DISCO Co., Ltd.)
[0341] Semiconductor wafer: 8-inch diameter (back ground to a thickness of 0.6 mm to 0.2 mm)
[0342] <Lamination conditions>
[0343] Attachment device: Trade name MA-3000III (Nitto Seiki Co., Ltd.)
[0344] Attachment speed: 10mm / min
[0345] Attachment pressure: 0.15MPa
[0346] Working table temperature during attachment: 70°C
[0347] <Cutting conditions>
[0348] Cutting device: Trade name DFD-6361 (DISCO Co., Ltd.)
[0349] Cutting ring: 2-8-1 (DISCO Co., Ltd.)
[0350] Cutting speed: 30mm / sec
[0351] Cutting blade: Z1: 203O-SE 27HCDD (DISCO Corporation)
[0352] Z2: 203O-S27HCBB (DISCO Co., Ltd.)
[0353] Cutting blade speed: Z1: 40000r / min
[0354] Z2: 45000r / min
[0355] Cutting method: step cutting
[0356] Wafer chip size: 1.0mm square
[0357] Cutting water supply: 2.0L / min
[0358] <Evaluation criteria for cutting properties>
[0359] S: The chip flying rate is 0% or more and less than 5%.
[0360] A: The chip flying rate is 5% or more and less than 10%.
[0361] B: The chip flying rate is 10% or more and less than 20%.
[0362] C: The chip flying rate is 20% or more.
[0363] (2) Pickup test (pickup performance)
[0364] After the mirror wafer is cut as described above, the semiconductor chip is picked up. Picking up is performed after the adhesive layer is irradiated with ultraviolet rays. The irradiation conditions are as follows. After irradiation with ultraviolet rays, the semiconductor chip with the adhesive sheet obtained by cutting is lifted up from the dicing tape side of the dicing / chip bonding integrated film with a needle, and picked up from the adhesive layer. At this time, the picking success rate (%) of the semiconductor chips (total number: 400) is calculated to evaluate the picking property. Therefore, the closer the picking rate is to 100%, the better the picking property. It should be noted that the chips that are scattered are not included in the base (parent number). The picking conditions are as follows.
[0365] <Ultraviolet irradiation conditions>
[0366] Ultraviolet (UV) irradiation device: High-pressure mercury lamp
[0367] UV irradiation cumulative light amount: 500mJ / cm2
[0368] Output: 75W
[0369] Irradiation intensity: 150mW / cm2
[0370] In addition, the ultraviolet ray irradiation was performed from the surface of the base material side of the dicing tape.
[0371] <Pickup conditions>
[0372] Pickup device: Trade name SPA-300 (Shinkawa Co., Ltd.)
[0373] Pick-up needle number: 1
[0374] Needle lifting speed: 20mm / sec
[0375] Needle lift: 500μm
[0376] Pickup time: 1 second
[0377] Cutting tape expansion: 3mm
[0378] <Evaluation Criteria>
[0379] S: The success rate of picking up is 95% or more and 100% or less.
[0380] A: The success rate of picking up is 80% or more and less than 95%.
[0381] B: The success rate of picking up is 60% or more and less than 80%.
[0382] C: The success rate of picking is less than 60%.
[0383] The adhesive sheets of Examples 1 to 7 had a small change rate in adhesive force and excellent water resistance. The dicing die-bonding integrated films produced using the adhesive sheets of Examples 1 to 7 showed good results in both the blade dicing test and the pickup test.
[0384] Industrial Applicability
[0385] According to the present disclosure, an adhesive composition can be provided, which can provide an adhesive sheet having high adhesive strength and excellent water resistance to cutting water, and whose adhesive strength is greatly reduced by irradiation with ultraviolet rays. An adhesive layer formed by the adhesive composition can be preferably used as a removable adhesive sheet, especially an adhesive layer of a dicing tape.
Claims
1. An adhesive composition comprising a (meth)acrylic resin A, a photopolymerization initiator B and a crosslinking agent C; The (meth)acrylic resin A is a diblock copolymer consisting of an X block and a Y block, The structural unit ratio of the X block and the Y block is 40:60 to 95:5 in terms of molar ratio, The X block comprises a structural unit M-1 having a hydroxyl group and a structural unit M-2 having an ethylenically unsaturated group, The Y block has an SP value of 20 (J / cm 3 ) 1 / 2 The following structural unit M-3 of the ethylenically unsaturated compound (m-3), and optionally one or more structural units selected from the structural unit M-1 having a hydroxyl group and the structural unit M-2 having an ethylenically unsaturated group, At least one of the structural unit M-1, the structural unit M-2, and the structural unit M-3 has a structure derived from a (meth)acryloyloxy group, When the total amount of the structural units of the X block is 100 mol %, the total amount of the structural units M-1 having a hydroxyl group and the structural units M-2 having an ethylenically unsaturated group in the X block is 18 to 95 mol %. When the total amount of the structural units of the Y block is 100 mol %, the total amount of the structural units M-1 having a hydroxyl group and the structural units M-2 having an ethylenically unsaturated group in the Y block is 0 to 17 mol %. 2 . The adhesive composition according to claim 1 , wherein the proportion of the structural unit M-2 having an ethylenically unsaturated group in the X block is 1 to 60 mol % when the total of the structural units of the X block is 100 mol %. 3 . The adhesive composition according to claim 1 , wherein the ratio of the structural unit M-1 having a hydroxyl group in the X block is 0.1 to 35 mol % when the total of the structural units of the X block is 100 mol %.
4. The adhesive composition according to claim 1, wherein the structural unit M-2 having an ethylenically unsaturated group in the X block is a structural unit formed by adding an ethylenically unsaturated compound a having an isocyanate group to a hydroxyl group of a structural unit derived from an ethylenically unsaturated compound m-1 having a hydroxyl group.
5. The adhesive composition according to claim 1, wherein the Y block has a SP value of 20 (J / cm 3 ) 1 / 2 The ratio of the structural unit M-3 of the following ethylenically unsaturated compound m-3 is 70 mol% or more.
6. The adhesive composition according to claim 1, wherein the Y block has a SP value of 20 (J / cm 3 ) 1 / 2 The structural unit M-3 of the following ethylenically unsaturated compound m-3 is a structural unit derived from a monomer selected from a linear or branched (meth)acrylic acid alkyl ester having an alkyl group of 6 to 30 carbon atoms, a (meth)acrylic acid ester having an alicyclic skeleton, and styrene. 7 . The adhesive composition according to claim 1 , wherein the Y block has a structural unit derived from styrene. 8 . The adhesive composition according to claim 1 , wherein the X block further comprises a structural unit derived from a linear or branched alkyl (meth)acrylate having an alkyl group with 1 to 5 carbon atoms.
9. The adhesive composition according to claim 1, wherein the weight average molecular weight of the (meth)acrylic resin A is 1×10 4 ~200×10 4 . 10 . The adhesive composition according to claim 1 , wherein the (meth)acrylic resin A has an ethylenically unsaturated group equivalent of 100 to 5000 g / mol. 11 . The adhesive composition according to claim 1 , wherein the (meth)acrylic resin A has a hydroxyl value of 0.01 to 50 mgKOH / g. 12 . A pressure-sensitive adhesive sheet comprising a substrate layer and a pressure-sensitive adhesive layer formed from a thermally cured product or a photothermocured product of the pressure-sensitive adhesive composition according to claim 1 . 13 . A dicing tape comprising a substrate layer and an adhesive layer formed of a thermally cured product or a photothermocured product of the adhesive composition according to claim 1 . 14 . A dicing die-bonding integrated film comprising, in this order, a base layer, a pressure-sensitive adhesive layer formed of a thermally cured product or a photothermocured product of the pressure-sensitive adhesive composition according to claim 1 , and an adhesive layer.
Citation Information
Patent Citations
Dicing tape and semiconductor wafer processing method
JP2012216841A
Dicing tape
CN107112221A
Dicing tape for integrated dicing and die-bonding tape
JP2015126217A
Acrylic resin, acrylic adhesive composition, adhesive sheet
JP2017066372A
Dicing tape and dicing die bond film
JP2020194878A